Composite lithium supplementing material, preparation method thereof and secondary battery
By using composite lithium supplement material in lithium-ion batteries, combining the mixture of conductive agents, dispersants and catalysts and the conductive network of cellulose nanocrystals, the problems of poor conductivity and high deliquesing voltage of lithium supplement material in lithium-ion batteries are solved. , improving the lithium replenishment performance and safety of the battery.
Patent Information
- Application Number
- CN202411383039.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
AI Technical Summary
The existing lithium-ion battery supplementary materials have poor conductivity, high deliquefaction voltage and residual alkali problems, resulting in a degradation of the safety performance and circulation performance of the secondary battery.
Using composite lithium supplement material, secondary particles are formed by mixing conductive agents, dispersants and catalysts with lithium-rich particles, cellulose nanocrystals shuttle to form conductive networks, superlattice catalysts fill the particle gaps, and a modified layer is formed on the surface. and ion-conducting layer to improve conductivity and dispersion performance.
It reduces the transmission impedance of active lithium ions, improves lithium replenishment performance, reduces the deliquification voltage, and enhances the safety and cycle stability of the battery.
Smart Images

Figure CN119297233A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a composite lithium supplement material and a preparation method thereof, and a secondary battery. Background Art
[0002] Lithium replenishment technology for lithium-ion batteries is one of the important means to solve the loss of active lithium and improve battery performance. The methods of lithium replenishment for lithium-ion batteries are mainly divided into negative electrode replenishment and positive electrode replenishment. Negative electrode replenishment materials require harsh environmental conditions during preparation and have greater safety risks during use, which restricts the promotion and application of negative electrode replenishment. Positive electrode replenishment has higher safety and operability because it does not require direct use of metallic lithium.
[0003] However, most common lithium-supplementing materials still have physical and chemical performance defects such as poor conductivity and high decomposition voltage of lithium decomposition. In addition, the materials often contain a large amount of residual alkali that cannot be effectively eliminated, which results in a decrease in the safety and cycle performance of secondary batteries when the lithium-supplementing materials are used in secondary batteries. Summary of the invention
[0004] In view of this, the present application provides a composite lithium supplement material and a preparation method thereof, and a secondary battery. The composite lithium supplement material has good conductivity, ion conductivity, dispersion performance or lower decomposition voltage of lithium decomposition, so that the composite lithium supplement material has good coating performance and processing performance.
[0005] The present application provides a composite lithium-supplementing material, which includes secondary particles, wherein the secondary particles include multiple primary particles and functional additives, at least part of the functional additives are distributed between the multiple primary particles, the primary particles are lithium-rich particles, and the functional additives include one or more of a conductive agent, a dispersant, and a catalyst.
[0006] Furthermore, the functional additive is selected from a conductive agent, and the conductive agent includes cellulose nanocrystals, and the cellulose nanocrystals shuttle between gaps between a plurality of primary particles to form a conductive network.
[0007] Furthermore, the cellulose nanocrystal is a one-dimensional material, the diameter D of the one-dimensional material satisfies the range: 5nm≤D<200nm, the length L of the one-dimensional material satisfies the range: 20nm≤L≤1000nm, and / or the particle size D' of the secondary particles satisfies the range: 0.3μm≤D'≤500μm.
[0008] Furthermore, the functional additive is selected from a catalyst, the catalyst includes a superlattice catalyst, the catalyst is in a granular form, and the catalyst is filled between the gaps of the plurality of primary particles.
[0009] Furthermore, the superlattice catalyst is a stacked structure, comprising a plurality of metal compound layers and at least one intercalation layer, wherein the metal compound layer and the intercalation layer both extend along a first direction, and along a second direction, the intercalation layer is inserted between two adjacent metal compound layers, the metal compound layer and the intercalation layer are arranged alternately, and the intercalation layer comprises a carbon layer, wherein the first direction and the second direction intersect.
[0010] Furthermore, the superlattice catalyst also includes a carbon substrate, and the multiple metal compound layers and at least one intercalation layer are arranged on the surface of the carbon substrate.
[0011] Furthermore, the functional additive is selected from a dispersant, the dispersant includes an anchoring group and a polymer segment, the anchoring group is connected to the surface of the primary particle, one end of the polymer segment is connected to the anchoring group, and the other end of the polymer segment extends in a direction away from the anchoring group.
[0012] Furthermore, the composite lithium supplement material further comprises a coating layer, the coating layer is coated on the outer surface of the secondary particle, and the modified layer comprises an acid-base complex containing lithium and / or an ion-conducting material.
[0013] The present application also provides a method for preparing a composite lithium-supplementing material, the preparation method comprising: providing functional additives and primary particles, wherein the primary particles are lithium-rich particles, and the functional additives include one or more of a conductive agent, a dispersant and a catalyst; mixing and dispersing the functional additives with the primary particles so that at least part of the functional additives are distributed between multiple primary particles to obtain secondary particles.
[0014] The present application also provides a secondary battery, which includes a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode includes the composite lithium supplement material and / or the composite lithium supplement material prepared by the preparation method of the composite lithium supplement material.
[0015] In this embodiment, the composite lithium supplement material includes secondary particles, and the secondary particles are composited by multiple primary particles and functional additives, so that the secondary particles have both a large lithium content and good physical and chemical properties. Among them, the functional additives include one or more of a conductive agent, a dispersant and a catalyst, so that the secondary particles have good conductivity, dispersion, ion conductivity or a lower decomposition voltage of lithium removal. When the composite lithium supplement material is applied to the positive electrode material and assembled in a secondary battery, the impedance of active lithium ion transmission in the secondary battery can be reduced, thereby improving the lithium supplement performance of the composite lithium supplement material. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the implementation will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 This is a schematic structural diagram of the composite lithium supplement material of the first embodiment of the present application;
[0018] Figure 2 This is a schematic structural diagram of a composite lithium supplement material according to a second embodiment of the present application;
[0019] Figure 3 This is a schematic structural diagram of a catalyst according to an embodiment of the present application;
[0020] Figure 4 Schematic diagram of a process for preparing a composite lithium supplement material according to an embodiment of the present application.
[0021] Description of reference numerals:
[0022] 100-composite lithium supplement material, 110-secondary particles, 112-primary particles, 113-cellulose nanocrystals, 114-superlattice catalyst, 1141-metal compound layer, 1142-intercalation layer, 115-dispersant, 1151-anchoring group, 1152-polymer segment, 120-modified layer, 130-ion-conducting layer, 140-coating layer. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0024] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.
[0025] Reference to "embodiment" or "implementation" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment or implementation may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0026] In lithium-ion batteries, lithium ions mainly originate from the positive electrode active material and are transferred to the negative electrode during the first charge, while forming a stable solid electrolyte film (Solid Electrolyte Interphase, SEI) on the surface of the negative electrode. The formation of the SEI film requires the irreversible consumption of a portion of the active lithium, resulting in a decrease in battery capacity and energy density. Lithium replenishment is a common technology for improving the performance of lithium-ion batteries. By introducing additional lithium ions into the battery, the loss of active lithium during the first charge can be compensated, thereby increasing the energy density of lithium-ion batteries.
[0027] Lithium replenishment technology for lithium-ion batteries is one of the important means to solve the loss of active lithium and improve battery performance. The methods of lithium replenishment for lithium-ion batteries are mainly divided into negative electrode replenishment and positive electrode replenishment. Negative electrode replenishment materials require harsh environmental conditions during the preparation process and have greater safety risks during use, which restricts the promotion and application of negative electrode replenishment. Positive electrode replenishment technology is a technology that replenishes lithium by adding additional lithium replenishment materials to the positive electrode active material. Positive electrode replenishment has higher safety and operability because it does not require direct use of metallic lithium.
[0028] However, most common lithium supplement materials still have physical and chemical performance defects such as poor conductivity and high lithium decomposition voltage, and the materials often contain a large amount of residual alkali that cannot be effectively eliminated, which leads to a decrease in the safety and cycle performance of secondary batteries when lithium supplement materials are used in secondary batteries. Therefore, how to improve the conductivity and physical and chemical properties of lithium supplement materials has become the key.
[0029] In addition, it is known that during the preparation of lithium-rich particles, the lithium source in the lithium-rich particles may react with oxygen, carbon dioxide or water vapor in the air to generate residual alkali such as lithium hydroxide, lithium carbonate, etc. If the content of the residual alkali is too high, when the lithium-rich particles are coated on the pole piece and applied to the battery, a gel-like substance may form on the surface or inside of the pole piece. This gel-like substance will hinder the transmission path of lithium ions and increase the difficulty of coating the lithium-rich particles. In addition, the residual alkali may react with the electrolyte, reducing the stability of the electrolyte.
[0030] See also Figure 1 and Figure 2The present application provides a composite lithium-supplementing material 100, which includes secondary particles 110, and the secondary particles 110 include multiple primary particles 112 and functional additives, at least part of the functional additives are distributed between the multiple primary particles 112, the primary particles 112 are lithium-rich particles, and the functional additives include one or more of a conductive agent, a dispersant 115 and a catalyst.
[0031] It is understandable that at least part of the functional additives are distributed between the plurality of primary particles 112 . The functional additives may be distributed in the gaps between the plurality of primary particles 112 , and / or the functional additives may be distributed on the surface of the primary particles 112 .
[0032] It can be understood that the primary particles 112 are original particles, and the multiple primary particles 112 are weakly bound to each other and grouped together, so that the multiple primary particles 112 are agglomerated to form secondary particles 110. Specifically, two primary particles 112 can be adjacent to each other, or two primary particles 112 can also be connected through functional additives, and primary particles 112 and primary particles 112, and primary particles 112 and functional additives can establish chemical connections or establish connections through physical binding forces (such as agglomeration), and the whole constitutes secondary particles 110.
[0033] Optionally, in Figure 1 In an embodiment, the functional additive is selected from the conductive agent; Figure 2 In an embodiment, the functional additive is selected from a dispersant 115 and a catalyst.
[0034] Optionally, in the secondary particles 110 , the functional additives are not limited to the conductive agent, the dispersant 115 and the catalyst, and the functional additives also include other materials, such as ion-conducting particles.
[0035] Optionally, a single secondary particle 110 may form a composite lithium-supplementing material 100 , and a plurality of secondary particles 110 may also form a composite lithium-supplementing material.
[0036] In this embodiment, the composite lithium supplement material 100 includes secondary particles 110, and the secondary particles 110 are composited by multiple primary particles 112 and functional additives, so that the secondary particles 110 have both a large lithium content and good physical and chemical properties. Among them, the functional additives include one or more of a conductive agent, a dispersant 115 and a catalyst, so that the secondary particles 110 have good conductivity, dispersion or a lower decomposition voltage. When the composite lithium supplement material 100 is applied to a positive electrode material and assembled in a secondary battery, the impedance of active lithium ion transmission in the secondary battery can be reduced, thereby improving the lithium supplement performance of the composite lithium supplement material 100.
[0037] It can be understood that in the terminology of the present application, "lithium replenishment performance" refers to the ability of the composite lithium replenishment material 100 to replenish lithium ions in the secondary battery. Specifically, during the first charge and discharge process of the secondary battery, due to the formation of the solid electrolyte interface (SEI) film, a large amount of lithium ions from the positive electrode will be permanently consumed, resulting in a low coulombic efficiency of the first cycle, reducing the capacity and energy density of the secondary battery, and in the subsequent charge and discharge process, in order to ensure the integrity of the SEI film, the lithium ions of the positive electrode will continue to be consumed. Therefore, a composite lithium replenishment material 100 containing primary particles 112 is provided at the positive electrode to replenish lithium ions to the secondary battery to replenish the consumed lithium ions, so that the secondary battery has a higher energy density, first cycle efficiency and a longer service life.
[0038] In the first embodiment of the present application, the functional additive is selected from a conductive agent, and the conductive agent includes cellulose nanocrystals 113 . The cellulose nanocrystals 113 shuttle between the gaps between the primary particles 112 and form a conductive network.
[0039] It can be understood that the cellulose nanocrystals 113 shuttle between the gaps between the primary particles 112 , and the cellulose nanocrystals 113 can be dispersed on the surface of the primary particles 112 and also dispersed between the primary particles 112 .
[0040] Optionally, cellulose nanocrystals 113 (Cellulose Nanocrystals, CNCs) are nano-scale cellulose extracted from natural fibers, have the characteristics of nanomaterials, and also have excellent optical and mechanical properties and biocompatibility.
[0041] Optionally, the preparation method of the cellulose nanocrystals 113 includes but is not limited to chemical method, mechanical method or biological method.
[0042] In this embodiment, the functional additive is selected from a conductive agent, and the conductive agent includes cellulose nanocrystals 113, which have good electronic conductivity and ionic conductivity. The cellulose nanocrystals 113 establish an electronic transmission network in the secondary particles 110 to form a conductive network and construct an ion transmission network. The cellulose nanocrystals 113 are dispersed on the surface of the primary particles 112, and the cellulose nanocrystals 113 are conducive to shortening the transmission path of lithium ions passing through the primary particles 112, thereby increasing the rate at which the lithium ions move in the secondary particles 110, so that the lithium ions of the primary particles 112 can escape from the composite lithium supplement material 100 and move to the electrolyte, and finally supplement lithium on the negative electrode side, so that the composite lithium supplement material 100 has good conductivity and lithium supplement performance.
[0043] Optionally, in some embodiments, the cellulose nanocrystal 113 is prepared by sulfuric acid hydrolysis, so that the surface of the cellulose nanocrystal 113 contains sulfonic acid groups, and the sulfonic acid groups can be used to anchor lithium ions, so as to stably attach lithium ions to the surface of the cellulose nanocrystal 113. When there is a secondary battery or a concentration gradient, the lithium ions will jump from one position to another, that is, from the donor to the acceptor, under the action of the electric field force or the concentration gradient, to achieve the conduction of lithium ions on the cellulose nanocrystal 113. In other words, when the surface of the cellulose nanocrystal 113 contains sulfonic acid groups, it is beneficial to improve the conduction efficiency of lithium ions, thereby improving the ionic conductivity.
[0044] Optionally, the surface of the cellulose nanocrystal 113 is a porous structure, which is convenient for absorbing and storing the solvent in the electrolyte, so as to increase the contact area and permeation channel between the cellulose nanocrystal 113 and the solvent in the electrolyte, which is beneficial to enhance the transfer of lithium ions between the electrolyte and the cellulose nanocrystal 113, and enhance the efficiency of lithium ion transmission between the cellulose nanocrystal 113 and the electrolyte.
[0045] In some embodiments, the cellulose nanocrystal 113 is a one-dimensional material, and the diameter D of the one-dimensional material satisfies the range: 5 nm ≤ D < 200 nm.
[0046] Specifically, the value of the diameter D of the one-dimensional material can be, but is not limited to, 5nm, 8nm, 10nm, 20nm, 40nm, 50nm, 80nm, 100nm, 110nm, 120nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm and 195nm, etc.
[0047] It can be understood that the cellulose nanocrystal 113 is a one-dimensional material, and the cellulose nanocrystal 113 may be in a rod-like structure or a needle-like structure.
[0048] In this embodiment, the cellulose nanocrystal 113 is a one-dimensional material, and a plurality of the one-dimensional materials are stacked to form a crystal. In the crystal formed by the stacking of the plurality of one-dimensional materials, there are also gaps, which are convenient for absorbing and storing the solvent in the electrolyte, so as to increase the contact area and permeation channel between the cellulose nanocrystal 113 and the solvent in the electrolyte, which is conducive to improving the transfer of lithium ions between the electrolyte and the cellulose nanocrystal 113, and improving the efficiency of lithium ion transmission between the cellulose nanocrystal 113 and the electrolyte. When the diameter of the one-dimensional material satisfies the range of 5nm≤D<200nm, the diameter of the one-dimensional material is within a reasonable range. On the one hand, it is conducive to the rapid transmission of lithium ions inside the cellulose nanocrystal 113, and the cellulose nanocrystal 113 has a suitable specific surface area, which can absorb and store more electrolyte solvents, and facilitate the rapid transmission of lithium ions between the cellulose nanocrystal 113 and the electrolyte. On the other hand, the one-dimensional material has good structural stability, so that the conductive network formed by the cellulose nanocrystal 113 has good stability. When the diameter of the one-dimensional material is too large, the cellulose nanocrystals 113 with too large a diameter have too small a specific surface area, which reduces the contact area and permeation channel between the cellulose nanocrystals 113 and the solvent in the electrolyte, and reduces the efficiency of lithium ion transmission between the cellulose nanocrystals 113 and the electrolyte. When the diameter of the one-dimensional material is too small, the one-dimensional material is too thin, which may reduce the structural stability of the cellulose nanocrystals 113 formed by the one-dimensional material. During the charge and discharge process of the secondary battery, the conductive network formed by the cellulose nanocrystals 113 may break or agglomerate, thereby affecting the stability of the conductive network formed by the cellulose nanocrystals 113.
[0049] Optionally, the length L of the one-dimensional material satisfies the range: 20nm≤L≤1000nm.
[0050] Specifically, the value of the length L of the one-dimensional material can be, but is not limited to, 20nm, 80nm, 100nm, 150nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 750nm, 800nm, 850nm, 900nm and 1000nm, etc.
[0051] In this embodiment, when the length L of the one-dimensional material satisfies the range: 20nm≤L≤1000nm, the length of the conductive channel inside the cellulose nanocrystal 113 is within a reasonable range, which is convenient for electrons and lithium ions to be quickly transmitted between the primary particles 112, and the one-dimensional material has good mechanical strength, so that the conductive network formed by the one-dimensional material stacking also has good structural stability. When the length L of the one-dimensional material is too long, the internal resistance of the cellulose nanocrystal 113 may increase, reducing the efficiency of the transmission of electrons and lithium ions between the cellulose nanocrystal 113 and the electrolyte, and the one-dimensional material that is too long is easy to break, and cannot be well inserted in the gap of the primary particle 112, so that the one-dimensional material has poor binding performance with the primary particle 112, and reduces the structural stability of the conductive network formed by the one-dimensional material stacking. When the length L of the one-dimensional material is too short, the length of the conductive channel inside the cellulose nanocrystal 113 is too short, which is not conducive to the rapid transmission of electrons and lithium ions between the primary particles 112, and reduces the efficiency of the transmission of electrons and lithium ions between the primary particles 112.
[0052] In some embodiments, the chemical formula of the cellulose nanocrystal 113 is: (C6H 10 O5) n , wherein n satisfies the range: 100≤n≤1000. Specifically, the value of n can be, but is not limited to, 100, 150, 200, 300, 400, 500, 600, 700, 800, 900, 1000, etc.
[0053] In this embodiment, when the chemical formula of the cellulose nanocrystal 113 is (C6H 10 O5) n , and n satisfies the range: 100≤n≤1000, the cellulose nanocrystal 113 has good electronic conductivity and ionic conductivity. When the cellulose nanocrystal 113 is disposed on the secondary particle 110, the cellulose nanocrystal 113 establishes an electronic transmission network in the secondary particle 110 to form a conductive network, and constructs an ion transmission network. When the primary particle 112 is dispersed on the cellulose nanocrystal 113, the transmission path of the lithium ions of the primary particle 112 can be shortened, thereby increasing the rate at which the lithium ions move in the cellulose nanocrystal 113, so that the lithium ions of the primary particle 112 can escape from the composite lithium supplement material 100 and move to the electrolyte, and finally supplement lithium on the negative electrode side, so that the composite lithium supplement material 100 has good conductivity and lithium supplement performance.
[0054] In some embodiments, the particle size D' of the secondary particles 110 satisfies the range of 0.3 μm≤D'≤500 μm.
[0055] Specifically, the particle size D' of the secondary particles 110 can be, but is not limited to, 0.3 μm, 1 μm, 10 μm, 20 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, 200 μm, 220 μm, 250 μm, 280 μm, 350 μm, 380 μm, 400 μm, 420 μm, 450 μm, 480 μm and 500 μm, etc.
[0056] In this embodiment, when the particle size D' of the secondary particle 110 satisfies the range of 0.3μm≤D'≤500μm, the particle size of the secondary particle 110 is within a reasonable range, the path of lithium ion embedding and de-embedding the secondary particle 110 is within a reasonable range, and the specific surface area of the secondary particle 110 is within a reasonable range, which can avoid side reactions with the electrolyte to generate products and increase impedance, and the composite lithium supplement material 100 has good ion conductivity and electrical conductivity. When the particle size of the secondary particle 110 is too large, the longer the diffusion path of the lithium ions in the secondary particle 110 during the charge and discharge process, the greater the resistance of the lithium ions of the secondary particle 110 to de-embedding from the secondary particle 110, which reduces the efficiency of the lithium ions of the secondary particle 110 to successively de-embedding the secondary particle 110, the modified layer 120 to enter the electrolyte, and embedding into the negative electrode side, thereby reducing the lithium supplement performance of the composite lithium supplement material 100. When the particle size of the secondary particles 110 is too small, the specific surface area of the secondary particles 110 is too large, which increases the contact area between the solvent in the electrolyte and the secondary particles 110, thereby consuming more charge and causing side reactions, ultimately increasing the impedance of the composite lithium supplement material 100 when used in a secondary battery.
[0057] Optionally, the lithium ion content in the primary particles 112 is relatively high. When the primary particles 112 are applied to the composite lithium supplement material 100 and assembled in a secondary battery, during the charge and discharge process of the secondary battery, the primary particles 112 can release more lithium ions and transmit them to the negative electrode side through the electrolyte to achieve lithium supplementation, thereby replenishing the consumed active lithium ions, improving the performance of the composite lithium supplement material 100 and increasing the energy density of the secondary battery.
[0058] In some embodiments, the primary particles include a ternary lithium-rich compound having a chemical formula of Li x1 M y1 O z1, wherein M is at least one element selected from Fe, Ni, Mn, Cu, Zn, Co, Cr, Zr, Sb, Ti, V, Mo, and Sn, 1≤x1≤8, 0<y1, 0<z1<7. In a specific embodiment, the lithium-rich material may be Li5FeO4, Li6MnO4, Li6CoO4, Li6ZnO4, Li2NiO2, Li2CuO2, Li2CoO2, Li2MnO2, Li2Ni 0.5 Mn 1.5 O4、Li2Ni d Cu (1-u) At least one of O2 (0<u<1), etc.
[0059] In some embodiments, the primary particles include a binary lithium-rich compound having a chemical formula of Li x2 M y2 , wherein M is one or more elements selected from S, P, I, Br, F, O, B, and Se, 1≤x2≤5, and 0<y2. In a specific embodiment, the lithium-rich material may be one or more selected from lithium sulfide (Li2S), lithium phosphide (Li3P), lithium iodide (LiI), and lithium bromide (LiBr).
[0060] The lithium-rich materials mentioned above may be undoped or modified by doping, or may be surface coated, pre-lithiated, etc. When the lithium-rich materials are used as positive electrode active materials, they may also be a combination of the lithium-rich materials listed above and conventional positive electrode materials such as lithium iron phosphate and ternary positive electrode materials.
[0061] Optionally, the composite lithium supplement material 100 further includes a coating layer 140 , which is coated on the outer surface of the secondary particle 110 , and the coating layer 140 includes an acid-base complex containing lithium and / or an ion-conducting material.
[0062] Optionally, in some embodiments, the coating layer 140 includes an acid-base complex containing lithium, and the acid-base complex containing lithium forms a modified layer 120 on the surface of the secondary particle 110, and the coating layer 140 is a modified layer 120; in other embodiments, the coating layer 140 includes an ion-conducting material, and the ion-conducting material forms an ion-conducting layer 130 on the periphery of the secondary particle 110, and the coating layer 140 includes an ion-conducting layer 130; in some further embodiments, the coating layer 140 includes an acid-base complex containing lithium and an ion-conducting material, and the coating layer 140 includes a modified layer 120 and an ion-conducting layer 130, and in the composite lithium supplement material 100, the secondary particle 110, the modified layer 120 and the ion-conducting layer 130 are arranged in sequence.
[0063] In this embodiment, the coating layer 140 is coated on the periphery of the secondary particle 110. When the coating layer 140 contains an acid-base complex of lithium, that is, the coating layer 140 includes a modified layer 120, specifically, the modified layer 120 is formed by modifying the secondary particle 110 with Lewis acid gas or the acidic anchoring group 1151 and accumulating the reactants generated in the modification process. Specifically, during the generation of the composite lithium supplement material 100, there is residual alkali such as lithium hydroxide, lithium carbonate, etc. on the surface of the primary particle 112. The secondary particle 110 is modified by at least one of Lewis acid gas such as phosphorus pentafluoride, boron trifluoride, etc. or at least one of the acidic anchoring groups 1151 such as -COOH, Ar-OH and -SO3H to form an acid-base complex containing lithium such as lithium carbonate, etc., and the modified layer 120 is accumulated on the surface of the secondary particle 110. On the one hand, the Lewis acid and / or anchoring group 1151 removes the residual alkali on the surface of the primary particle 112 of the secondary particle 110 during the modification of the secondary particle 110, so that when the composite lithium supplement material 100 is applied to the positive electrode, it can avoid the formation of gel-like substances on the surface or inside of the positive electrode, avoid increasing the transmission path of lithium ions and increase the coating difficulty of the composite lithium supplement material 100, and avoid the side reaction of residual alkali with the electrolyte, thereby improving the lithium supplement performance, processing performance and safety performance of the composite lithium supplement material 100. On the other hand, the modified layer 120 can also be used as a coating layer and coated on the surface of the secondary particle 110 to prevent the electrolyte from directly contacting the primary particle 112 and increase the service life of the composite lithium supplement material 100. Furthermore, the modified layer 120 includes an acid-base complex containing lithium. When the composite lithium-supplementing material 100 is applied to a secondary battery and during the charge and discharge process of the secondary battery, the modified layer 120 facilitates the insertion and extraction of lithium ions, which can further improve the lithium-supplementing performance of the composite lithium-supplementing material 100. The composite lithium-supplementing material 100 obtained in this embodiment has good electrical conductivity and ion conductivity, and the primary particles 112 contain less or no residual alkali, so that the composite lithium-supplementing material 100 has good coating performance and use performance. Furthermore, the composite lithium-supplementing material 100 has good electrical conductivity, which is convenient for reducing the delithiation potential of the composite lithium-supplementing material 100, so that the composite lithium-supplementing material 100 can be applied to more secondary batteries to supplement lithium for secondary batteries.
[0064] Furthermore, when the coating layer 140 includes an ion-conducting material, the ion-conducting material forms an ion-conducting layer 130 on the periphery of the secondary particle 110. In other words, the modified layer 120 includes the ion-conducting layer 130. In this embodiment, the ion-conducting layer 130 is disposed on the periphery of the secondary particle 110, which is equivalent to disposing another coating layer on the periphery of the secondary particle 110 to prevent the modified layer 120 from rupturing and causing other substances in the electrolyte to directly contact the primary particle 112. The ion-conducting layer 130 acts as a buffer layer between the cellulose nanocrystals 113 and the electrolyte, so that the composite lithium supplement material 100 has a higher stability. When the composite lithium supplement material 100 is applied to a secondary battery, it is beneficial to stabilize the interface structure between the positive electrode and the electrolyte, thereby reducing the side reaction between the electrolyte and the composite lithium supplement material 100 and improving the cycle stability of the secondary battery.
[0065] Optionally, the modified layer 120 is formed by modifying the secondary particles 110 with Lewis acid gas and accumulating reactants generated during the modification process.
[0066] During the generation process of the composite lithium-supplementing material 100, there is residual alkali such as lithium hydroxide, lithium carbonate, etc. on the surface of the primary particle 112. The secondary particle 110 is modified by at least one of Lewis acid gases such as phosphorus pentafluoride, boron trifluoride, etc. Phosphorus pentafluoride or boron trifluoride reacts with residual alkali lithium hydroxide, lithium carbonate, etc. to generate acid-base complexes containing lithium such as lithium phosphate, lithium borate, etc., and accumulates on the surface of the secondary particle 110 to form the modified layer 120. On the one hand, in the process of modifying the secondary particles 110 with Lewis acids such as phosphorus pentafluoride and boron trifluoride, the Lewis acids first react with lithium hydroxide, lithium carbonate, etc. to neutralize the acid and base to remove the residual alkali on the surface of the primary particles 112 of the secondary particles 110, so that when the composite lithium supplement material 100 is applied to the positive electrode, it can avoid the formation of gel-like substances on the surface or inside of the positive electrode, avoid increasing the transmission path of lithium ions and increase the coating difficulty of the composite lithium supplement material 100, and avoid the side reaction of residual alkali with the electrolyte, thereby improving the lithium supplement performance, processing performance and safety performance of the composite lithium supplement material 100. On the other hand, the modified layer 120 can also be used as a coating layer and coated on the surface of the secondary particles 110 to prevent the electrolyte from directly contacting the primary particles 112 and increase the service life of the composite lithium supplement material 100. Furthermore, the modified layer 120 includes an acid-base complex containing lithium. When the composite lithium-supplementing material 100 is applied to a secondary battery and during the charge and discharge process of the secondary battery, the modified layer 120 facilitates the insertion and extraction of lithium ions, which can further improve the lithium-supplementing performance of the composite lithium-supplementing material 100. The composite lithium-supplementing material 100 obtained in this embodiment has good electrical conductivity and ion conductivity, and the primary particles 112 contain less or no residual alkali, so that the composite lithium-supplementing material 100 has good coating performance and use performance. Furthermore, the composite lithium-supplementing material 100 has good electrical conductivity, which is convenient for reducing the delithiation potential of the composite lithium-supplementing material 100, so that the composite lithium-supplementing material 100 can be applied to more secondary batteries to supplement lithium for secondary batteries.
[0067] It can be understood that the product generated by the acid-base neutralization reaction between Lewis acid and Lewis base is an acid-base complex.
[0068] It can be understood that in the embodiment of the present application, the chemical reaction formula of the Lewis acid gas such as phosphorus pentafluoride and boron trifluoride with the residual alkali on the surface of the primary particle 112 includes but is not limited to at least one of the following equations (1) to (4):
[0069] (1)PF5+4Li2CO3=Li3PO4+4CO2+5LiF
[0070] (2)PF5+8LiOH=Li3PO4+4H2O+5LiF
[0071] (3)BF3+3Li2CO3=3LiF+Li3BO3+CO2
[0072] (4)BF3+6LiOH=3LiF+Li3BO3+3H2O
[0073] In some embodiments, the thickness d2 of the modified layer 120 satisfies the range: 0.01 nm≤d2≤5 nm.
[0074] Specifically, the thickness d2 of the modified layer 120 may be, but is not limited to, 0.01 nm, 0.08 nm, 0.1 nm, 0.5 nm, 1 nm, 1.5 nm, 1.8 nm, 2 nm, 2.2 nm, 2.8 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, and 5 nm.
[0075] In this embodiment, when the thickness d2 of the modified layer 120 satisfies the range of 0.01nm≤d2≤5nm, the thickness of the modified layer 120 is within a reasonable range. On the one hand, the modified layer 120 can protect the secondary particles 110, and while facilitating the passage of lithium ions through the modified layer 120, avoid the structural strength of the modified layer 120 being too low and breaking, thereby ensuring the transmission performance of the lithium ions in the cellulose nanocrystals 113 and the electrolyte, and can effectively isolate the primary particles 112 and the electrolyte, avoiding excessive consumption of the primary particles 112 and the electrolyte due to side reactions. On the other hand, the modified layer 120 is formed by modifying the secondary particles 110 with Lewis acid gas or the acidic anchoring group 1151 and accumulating the reactants generated in the modification process. If the modified layer 120 is within a reasonable range, the Lewis acid gas and / or the acidic anchoring group 1151 can fully remove the residual alkali of the primary particles 112 during the modification of the secondary particles 110 by the Lewis acid gas, so that when the composite lithium supplement material 100 is applied to the positive electrode, it can avoid the formation of gel-like substances on the surface or inside of the positive electrode, avoid increasing the transmission path of lithium ions and increase the coating difficulty of the composite lithium supplement material 100, and avoid the side reaction of residual alkali with the electrolyte, thereby improving the lithium supplement performance, processing performance and safety performance of the composite lithium supplement material 100. When the thickness of the modified layer 120 is too large, it means that the Lewis acid gas or the acidic anchoring group 1151 corrodes the secondary particles 110 excessively, which may affect the lithium supplement performance of the primary particles 112. In addition, when the composite lithium supplement material 100 is applied to a secondary battery, the thicker the modified layer 120 is, the greater the resistance of the lithium ions in the primary particles 112 to pass through the modified layer 120, which is not conducive to the lithium ions from the cellulose nanocrystals 113 passing through the modified layer 120 and then passing through the electrolyte to the negative electrode side for lithium supplementation, thereby reducing the transmission efficiency of lithium ions. When the thickness of the modified layer 120 is too small, on the one hand, the too thin modified layer 120 is difficult to protect the secondary particles 110 from the erosion of the electrolyte. During the charge and discharge cycle of the secondary battery, the modified layer 120 may rupture and cause the primary particles 112 in the secondary particles 110 to be lost, thereby reducing the safety performance and cycle performance of the composite lithium supplement material 100 when applied to a secondary battery.On the other hand, the modified layer 120 is formed by the Lewis acid gas and / or the acidic anchoring group 1151 modifying the secondary particle 110 and accumulating the reactants generated in the modification process. If the modified layer 120 is too thin, the Lewis acid gas and / or the anchoring group 1151 may not fully remove the residual alkali of the primary particle 112 during the modification of the secondary particle 110, resulting in excessive residual alkali content on the surface of the primary particle 112. When the primary particle 112 is coated on the pole piece and applied to the secondary battery, a gel-like substance may be formed on the surface or inside of the pole piece. This gel-like substance will hinder the transmission path of lithium ions and increase the difficulty of coating the primary particle 112. In addition, the residual alkali may react with the electrolyte, reducing the stability of the electrolyte.
[0076] Optionally, in some embodiments, the modified layer 120 includes at least one of phosphate and fluoride. Phosphate and fluoride are acid-base complexes containing lithium, which are products generated by the neutralization reaction of Lewis acid gas and residual alkali. In this process, the residual alkali on the surface of the primary particle 112 is removed, so that when the composite lithium supplement material 100 is applied to the positive electrode, it can avoid the formation of gel-like substances on the surface or inside of the positive electrode, avoid increasing the transmission path of lithium ions and increase the coating difficulty of the composite lithium supplement material 100, and avoid the side reaction of residual alkali with the electrolyte, thereby improving the lithium supplement performance, processing performance and safety performance of the composite lithium supplement material 100.
[0077] In some embodiments, the modified layer 120 includes at least one of Li 3 PO 4 , LiF, and LiBF 4 .
[0078] In this embodiment, the modified layer 120 includes at least one of Li3PO4, LiF and LiBF4, wherein Li3PO4 and LiBF4 are acid-base complexes containing lithium, which are formed by acid-base neutralization reactions between Lewis acid gases such as phosphorus pentafluoride and boron trifluoride and lithium hydroxide, lithium carbonate, etc., respectively. LiF is another product generated in this reaction process. In this process, the residual alkali on the surface of the primary particles 112 is removed, so that when the composite lithium supplement material 100 is applied to the positive electrode, it can avoid the formation of gel-like substances on the surface or inside of the positive electrode, avoid increasing the transmission path of lithium ions and increase the coating difficulty of the composite lithium supplement material 100, and also avoid the residual alkali from having a side reaction with the electrolyte, thereby improving the lithium supplement performance, processing performance and safety performance of the composite lithium supplement material 100. In addition, Li3PO4, LiF and LiBF4 are all solid, which can isolate the cellulose nanocrystals 113 from the electrolyte to prevent other substances in the electrolyte from directly contacting the primary particles 112 and destroying the structure of the primary particles 112, which is beneficial to prolonging the service life of the composite lithium supplement material 100.
[0079] See also Figure 2 In some embodiments, the ion conductive layer 130 is coated on the periphery of the modified layer 120, and the ion conductivity σ of the ion conductive layer 130 satisfies the range: 10 -8 S / cm≤σ≤10 -2 S / cm.
[0080] It can be understood that the composite lithium supplement material 100 includes secondary particles 110 , a modified layer 120 and an ion conductive layer 130 , and the secondary particles 110 , the modified layer 120 and the ion conductive layer 130 are arranged in sequence from the inside to the outside.
[0081] Specifically, the value of the ionic conductivity σ of the ion conductive layer 130 may be, but is not limited to, 10 -8 S / cm, 8×10 -8 S / cm, 10 -7 S / cm, 5×10 -7 S / cm, 10 -6 S / cm, 8×10 -6 S / cm, 10 -5 S / cm, 5×10 -5 S / cm, 10 -4 S / cm, 8×10 -4 S / cm, 10 -3 S / cm, 8×10 -3 S / cm and 10 -2 S / cm, etc.
[0082] In this embodiment, the ion-conducting layer 130 is disposed on the periphery of the modified layer 120, which is equivalent to disposing another coating layer on the periphery of the modified layer 120 to prevent the modified layer 120 from rupturing and causing other substances in the electrolyte to directly contact the primary particles 112. The ion-conducting layer 130 acts as a buffer layer between the cellulose nanocrystals 113 and the electrolyte, so that the composite lithium supplement material 100 has higher stability. When the composite lithium supplement material 100 is applied to a secondary battery, it is beneficial to stabilize the interface structure between the positive electrode and the electrolyte, thereby reducing the side reaction between the electrolyte and the composite lithium supplement material 100 and improving the cycle stability of the secondary battery. In addition, the ionic conductivity σ of the ion-conducting layer 130 satisfies the range: 10 -8 S / cm≤σ≤10 -2S / cm, the ion-conducting layer 130 has good ion-conducting performance, which facilitates the lithium ions to enter the cellulose nanocrystals 113 from the electrolyte, and also facilitates the lithium ions of the primary particles 112 to escape and be transferred from the cellulose nanocrystals 113 to the electrolyte. The ion-conducting layer 130 is beneficial to reducing the interface impedance between the positive electrode and the electrolyte, thereby helping to improve the charge and discharge efficiency of the secondary battery and extend the service life of the secondary battery.
[0083] Optionally, the ion-conducting layer 130 is a lithium ion conductor layer, and the lithium ions can be freely embedded in or extracted from the ion-conducting layer 130 , thereby improving the efficiency of lithium replenishment of the composite lithium replenishing material 100 .
[0084] In some embodiments, the thickness d1 of the ion conductive layer 130 satisfies the range of 0.5 nm ≤ d1 ≤ 50 nm. Specifically, the thickness d1 of the ion conductive layer 130 may be, but is not limited to, 0.5 nm, 3 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 34 nm, 38 nm, 40 nm, 45 nm, 48 nm, and 50 nm.
[0085] It can be understood that the thickness of the ion conductive layer 130 is in the nanometer level.
[0086] In this embodiment, the thickness of the ion-conducting layer 130 is at the nanometer level. The nanometer-level size enables the ion-conducting layer 130 to have a finer ion channel, which is beneficial to reduce the obstacles in the transmission process of lithium ions in the ion-conducting layer 130, thereby improving the transmission efficiency of the lithium ions in the ion-conducting layer 130. In addition, the nanometer-level ion-conducting layer 130 can reduce the interface impedance between the ion-conducting layer 130 and the modified layer 120, so that the ion-conducting layer 130 can be more closely arranged on the periphery of the modified layer 120, thereby improving the structural stability of the composite lithium supplement material 100. When the thickness d1 of the ion-conducting layer 130 satisfies the range of 0.5nm≤d1≤50nm, the thickness of the ion-conducting layer 130 is within a reasonable range, and the lithium ions have a higher transmission efficiency in the ion-conducting layer 130, which is beneficial to the composite lithium supplement material 100 to release and transmit lithium ions during the lithium supplement process. When the thickness of the ion-conducting layer 130 is too large or too small, the ion-conducting performance of the ion-conducting layer 130 will be reduced, thereby reducing the efficiency of lithium ion transmission in the ion-conducting layer 130, affecting the release and transmission of lithium ions by the composite lithium-supplementing material 100 during the lithium-supplementing process. In addition, when the size of the composite lithium-supplementing material 100 is determined, if the thickness of the ion-conducting layer 130 is too large, it may also lead to a reduction in the secondary particles 110, thereby leading to a reduction in the primary particles 112, and reducing the energy density of the composite lithium-supplementing material 100.
[0087] Optionally, the ion-conducting material is selected from at least one of a metal ion conductor, a ceramic ion conductor, and a solid electrolyte.
[0088] In some embodiments, the ion-conducting material includes LiNbO3, Li4Ti5O 12 , LiAlO2, LiAlF4.
[0089] In this embodiment, the ion-conducting material includes LiNbO3, Li4Ti5O 12 , LiAlO2, LiAlF4, the ion-conducting material forms the ion-conducting layer 130, the ion-conducting layer 130 is a conductor layer of lithium ions, and lithium ions have a higher transmission efficiency in the ion-conducting layer 130.
[0090] In some embodiments, the ion conductive layer 130 is a deposition layer formed by atomic deposition.
[0091] In this embodiment, the ion-conducting layer 130 is a deposition layer formed by atomic deposition, which facilitates the control of the thickness of the ion-conducting layer 130 so that the thickness of the ion-conducting layer 130 is within a reasonable range, and the preparation process of the composite lithium-supplementing material 100 is simple and efficient. On the other hand, depositing the ion-conducting layer 130 on the periphery of the modified layer 120 is conducive to improving the bonding performance between the ion-conducting layer 130 and the modified layer 120, thereby improving the structural stability of the composite lithium-supplementing material 100, and finally improving the use performance of the composite lithium-supplementing material 100 and extending the service life of the composite lithium-supplementing material 100.
[0092] In some embodiments, the composite lithium supplement material 100 further includes ion-conducting particles, which are distributed on the secondary particles 110. In other words, the ion-conducting particles are deposited on the surface of the primary particles 112. The ion-conducting particles are selected from at least one of metal ion conductors, ceramic ion conductors, and solid electrolytes, and are specifically selected from LiNbO3, Li4Ti5O 12 , LiAlO2, LiAlF4.
[0093] In this embodiment, during the deposition of the ion-conducting layer 130 on the periphery of the modified layer 120, some ion-conducting particles may pass through the gaps in the modified layer 120 into the secondary particles 110, and deposit on the surface of the primary particles 112 or between multiple primary particles 112. The secondary particles 110 are formed by stacking and agglomeration of fine lithium-rich material particles, so there are more pores on the surface of the primary particles 112 or between multiple primary particles 112. The ion-conducting particles are deposited on the surface of the primary particles 112, which can fill the pores of the primary particles 112 and reduce the specific surface area of the primary particles 112, so as to reduce the interface impedance of the primary particles 112 in contact with the solvent in the electrolyte, thereby further improving the efficiency of ion transmission between the cellulose nanocrystals 113 and the electrolyte. When the composite lithium-supplementing material 100 is applied to secondary batteries, it is beneficial to improve the charging and discharging efficiency of the secondary batteries and extend the service life of the secondary batteries.
[0094] Optionally, in the second embodiment of the present application, the functional additive is selected from a catalyst, the catalyst includes a superlattice catalyst 114 , the catalyst is in a granular form, and the catalyst is filled between the gaps of the plurality of primary particles 112 .
[0095] It can be understood that the superlattice catalyst 114 is a catalyst having a superlattice structure formed by alternating arrangement of two or more different materials at the nanoscale.
[0096] It can be understood that the catalyst is filled in the gaps between the plurality of primary particles 112 , and the catalyst can also be disposed on the surface of the primary particles 112 .
[0097] In this embodiment, the functional additive is selected from a catalyst and the catalyst is a superlattice catalyst 114. The catalyst constructs an ion-conducting network and a conductive network, which can significantly reduce the diffusion barrier of lithium ions in the secondary particles 110, so as to achieve rapid movement of lithium ions in the secondary particles 110, thereby facilitating the lithium ions of the primary particles 112 to escape from the composite lithium supplement material 100 and move to the electrolyte, and finally replenish lithium on the negative electrode side, so that the composite lithium supplement material 100 has good electrical conductivity and lithium supplement performance. In addition, the catalyst is filled between the gaps of multiple primary particles 112, which is conducive to improving the dispersion uniformity of the catalyst and the primary particles 112, thereby improving the electrical conductivity and ion-conducting properties of the secondary particles 110, and finally improving the lithium supplement performance of the composite lithium supplement material 100.
[0098] Optionally, the particle size d3 of the superlattice catalyst 114 satisfies the range: 50nm≤d3≤5000nm.
[0099] Specifically, the value of the particle size d3 of the superlattice catalyst 114 can be but is not limited to 50nm, 80nm, 100nm, 150nm, 200nm, 300nm, 350nm, 400nm, 500nm, 600nm, 1000nm, 1200nm, 1500nm, 1800nm, 2000nm, 2200nm, 2500nm, 3000nm, 3200nm, 3500nm, 4000nm, 4500nm, 4800nm and 5000nm, etc.
[0100] In this embodiment, when the particle size d3 of the superlattice catalyst 114 satisfies the range: 50nm≤d3≤5000nm, the particle size of the superlattice catalyst 114 is within a reasonable range, so that the superlattice catalyst 114 is sufficient to construct an ion-conducting network and a conductive network, and can significantly reduce the diffusion barrier of lithium ions in the secondary particles 110, so as to achieve rapid movement of lithium ions in the secondary particles 110, thereby facilitating the lithium ions of the primary particles 112 to escape from the composite lithium supplement material 100 and move to the electrolyte, and finally replenish lithium on the negative electrode side, so that the composite lithium supplement material 100 has good conductivity and lithium supplement performance. In addition, it can be avoided that the particle size of the superlattice catalyst 114 is too large to reduce the contact area between the superlattice catalyst 114 and the primary particles 112, so that the superlattice catalyst 114 can fully play its role.
[0101] Optionally, see Figure 3 The superlattice catalyst 114 is a stacked structure, and the superlattice catalyst 114 includes a plurality of metal compound layers 1141 and at least one intercalation layer 1142, and the metal compound layers 1141 and the intercalation layer 1142 are arranged along a first direction (such as Figure 3 X direction) and extends along the second direction (as shown in Figure 3 In the embodiment of the present invention, the intercalation layer 1142 is inserted between two adjacent metal compound layers 1141, and the intercalation layer 1142 is an amorphous carbon layer, wherein the first direction and the second direction intersect. In other words, when the superlattice catalyst 114 includes a plurality of metal compound layers 1141 and a plurality of intercalation layers 1142, the metal compound layers 1141 and the intercalation layers 1142 are arranged alternately, and optionally, the first direction is perpendicular to the second direction.
[0102] It can be understood that, along the second direction, each of the intercalation layers 1142 is intercalated between two adjacent metal compound layers 1141 . In other words, the intercalation layer 1142 serves as an intercalation agent to be intercalated between two connected metal compound layers 1141 .
[0103] In this embodiment, the metal compound layer 1141 is arranged in sequence along the second direction, and the metal compound layer 1141 exists in a layered form, the atoms in the layer are connected by chemical bonds, and the layers interact with each other through weak van der Waals forces. This layered structure allows the metal compound layer 1141 to exhibit unique physical properties in terms of mechanics, optics, etc., and within a certain range, the metal compound layer 1141 exhibits good thermal stability, which is beneficial to improving the performance of the superlattice catalyst 114 and the composite lithium supplement material 100. Further, the intercalation layer 1142 is arranged between two adjacent metal compound layers 1141, which is beneficial to increase the distance between the two adjacent metal compound layers 1141, so that the larger interlayer spacing is more conducive to the passage of lithium ions, which can significantly reduce the diffusion barrier of lithium ions to achieve rapid movement of lithium ions. Furthermore, the intercalation layer 1142 includes a carbon layer, which can further improve the electrical conductivity of the metal compound layer 1141, and the metal compound layer 1141 and the intercalation layer 1142 are both layered structures. There is a large contact area between the metal compound layer 1141 and the intercalation layer 1142, which is beneficial to the widening of the lattice and the enhancement of the ion conductivity of the primary particle 112. In other words, the superlattice catalyst 114 improves the ion conductivity and electrical conductivity of the secondary particle 110, thereby comprehensively improving the lithium replenishment performance of the composite lithium replenishment material 100.
[0104] Optionally, in some embodiments, the metal compound layer 1141 includes at least one of molybdenum, nickel and sulfur. The metal compound layer 1141 includes molybdenum, nickel and sulfur, and molybdenum sulfide and nickel sulfide have high theoretical capacity when used as electrode materials, so that the superlattice catalyst 114 has a high theoretical capacity.
[0105] Optionally, in some embodiments, the intercalation layer 1142 is an amorphous carbon layer.
[0106] Optionally, in some other embodiments, the intercalation layer 1142 is a nitrogen-doped amorphous carbon layer. In other words, the intercalation layer 1142 includes nitrogen.
[0107] In this embodiment, the intercalation layer 1142 is a nitrogen-doped amorphous carbon layer. Compared with the undoped amorphous carbon layer, the nitrogen-doped amorphous carbon layer has better conductivity, so that the effect of the superlattice catalyst 114 in improving the conductivity of the secondary particles 110 is more significant.
[0108] Optionally, the superlattice catalyst 114 further includes a carbon substrate, and the plurality of metal compound layers 1141 and at least one of the intercalation layers 1142 are disposed on the surface of the carbon substrate.
[0109] Optionally, the carbon substrate may be, but is not limited to, graphene.
[0110] In this embodiment, the superlattice catalyst 114 is based on a carbon substrate, the metal compound layer 1141 and the intercalation layer 1142 are disposed on the surface of the carbon substrate, and part of the metal compound layer 1141 and / or the intercalation layer 1142 are embedded in the carbon substrate, and the carbon substrate serves as a substrate and a skeleton to construct a conductive network of the superlattice catalyst 114. When the composite lithium supplement material 100 is applied to a secondary battery and during charging or discharging, the carbon substrate serves as a substrate to effectively adjust the volume change of the composite lithium supplement material 100 during the process of lithium removal and lithium insertion, so as to avoid the structure of the composite lithium supplement material 100 from being destroyed, which is beneficial to prolonging the service life of the composite lithium supplement material 100.
[0111] In some embodiments, the primary particles include an organic lithium salt having a chemical formula of Li x1 C y1 O z1 , where 0<x1≤2,y1> 0, z1>0. Specifically, the organic lithium salt includes one or more of Li2C3O3, Li2C4O4, Li2C6O6, Li2C3O5, Li2C2O4 and Li2C4O6. In some embodiments, the primary particles may also include other lithium-rich compounds with higher decomposition voltages, mainly including lithium-supplementing materials with a delithiation potential of more than 4V, such as Li2O (delithiation potential 4.5V), Li2O2 (delithiation potential 4.3V), LiOH (delithiation potential 4.8V), Li4SiO4 (delithiation potential 4.5V), Li3PO4 (delithiation potential exceeds 4V), Li2CO3 (delithiation potential 4.7V), and Li5FeO4 (delithiation potential 4V).
[0112] The above-mentioned lithium-rich compounds all have high capacity, but these lithium-rich compounds require a higher charging voltage for delithiation, and there is a technical problem of high platform voltage. At the same time, the higher voltage also causes the lithium-rich compounds to produce oxygen when the lithium-ion battery is charged and discharged for the first time. The generated oxygen is further oxidized to cause the electrolyte to oxidize and decompose, thereby resulting in reduced safety and performance of the lithium-ion battery. These lithium-rich compounds with higher decomposition voltages are also difficult to compound with conventional positive electrode materials (such as lithium iron phosphate, whose delithiation potential is about 3.5V), which limits the widespread application of lithium-supplementing materials. Therefore, in some embodiments of the present application, the decomposition of lithium-rich materials can be effectively promoted and the decomposition voltage can be reduced through the action of a catalyst; further, the decomposition voltage of the lithium-rich compound is significantly reduced through the catalytic action of the fast electron / lithium ion transmission of the superlattice catalyst 114.
[0113] Optionally, in the second embodiment, the functional additive is also selected from a dispersant 115, the dispersant 115 includes an anchoring group 1151 and a polymer segment 1152, the multiple anchoring groups 1151 are connected to the surface of the primary particle 112, one end of the polymer segment 1152 is connected to the anchoring group 1151, and the other end of the polymer segment 1152 extends in a direction away from the primary particle 112.
[0114] Optionally, the anchoring group 1151 is selected from at least one of -COOH, Ar-OH and -SO3H, and the polymer segment 1152 is selected from at least one of polyolefin, polyester, polyacrylate and polyether.
[0115] It can be understood that in the second embodiment, the functional additives include the catalyst and the dispersant 115 .
[0116] It can be understood that the anchoring group 1151 is acidic, and the anchoring group 1151 is selected from -COOH (carboxyl group), Ar-OH (phenolic hydroxyl group) and -SO3H (sulfonic acid group).
[0117] In this embodiment, the functional additive includes the dispersant 115, and the dispersant 115 includes a plurality of anchoring groups 1151. During the generation of the composite lithium supplement material 100, residual alkali such as lithium hydroxide, lithium carbonate, etc. is present on the surface of the primary particle 112. The secondary particle 110 is modified by at least one of the anchoring groups 1151 such as -COOH, Ar-OH and -SO3H. At least one of -COOH, Ar-OH and -SO3H reacts with the residual alkali lithium hydroxide, lithium carbonate, etc. to generate an acid-base complex containing lithium, and accumulates on the surface of the secondary particle 110 to form the modified layer 120. The anchoring group 1151 undergoes an acid-base neutralization reaction with lithium hydroxide, lithium carbonate, etc. to remove the residual alkali on the surface of the primary particle 112 of the secondary particle 110, so that when the composite lithium supplement material 100 is applied to the positive electrode, it can avoid the formation of a gel-like substance on the surface or inside of the positive electrode, avoid increasing the transmission path of lithium ions and increase the difficulty of coating the composite lithium supplement material 100, and also avoid the residual alkali from having a side reaction with the electrolyte, thereby improving the lithium supplement performance, processing performance and safety performance of the composite lithium supplement material 100. Furthermore, the dispersant 115 further includes a polymer segment 1152, which is fixed to the surface of the primary particle 112 through the anchoring group 1151 and the other end of the polymer segment 1152 extends in a direction away from the primary particle 112, and the plurality of polymer segments 1152 are suspended on the periphery of the plurality of primary particles 112 to form a three-dimensional obstacle, so that when the plurality of secondary particles 110 and / or the primary particles 112 are close to each other, the plurality of secondary particles 110 and / or the plurality of primary particles 112 repel each other, so that the composite lithium supplement material 100 has a higher dispersion performance. When the composite lithium supplement material 100 has a better dispersion performance, the viscosity of the slurry is lower during the preparation of the slurry, which can play a role in reducing the solid content of the slurry, thereby reducing the amount of nitrogen-methylpyrrolidone, so as to achieve the effect of reducing costs and increasing efficiency, and at the same time, the quality of the slurry can be improved, and the processing performance of the composite lithium supplement material 100 can be improved.
[0118] It can be understood that the product generated by the acid-base neutralization reaction between the anchoring group 1151 and the Lewis base is an acid-base complex.
[0119] Optionally, in the second embodiment of the present application, when the secondary particles 110 include a dispersant 115, and the dispersant 115 includes an anchoring group 1151 and a polymer segment 1152, then in the secondary particles 110, the ratio of the sum of the masses of the plurality of primary particles 112 to the sum of the masses of the plurality of anchoring groups 1151 satisfies the range of 500 to 1000, and the ratio of the sum of the masses of the plurality of primary particles 112 to the sum of the masses of the plurality of polymer segments 1152 satisfies the range of 5 to 20.
[0120] Specifically, the ratio of the sum of the masses of the plurality of primary particles 112 to the sum of the masses of the plurality of anchoring groups 1151 may be, but is not limited to, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, etc.
[0121] Specifically, the ratio of the sum of the masses of the plurality of primary particles 112 to the sum of the masses of the plurality of polymer segments 1152 may be, but is not limited to, 5, 6, 8, 9, 10, 12, 13, 15, 16, 18, 19, 20, etc.
[0122] In this embodiment, in the secondary particles 110, when the ratio of the sum of the masses of the plurality of primary particles 112 to the sum of the masses of the plurality of anchoring groups 1151 satisfies the range of 500 to 1000, and the ratio of the sum of the masses of the plurality of primary particles 112 to the sum of the masses of the plurality of polymer segments 1152 satisfies the range of 5 to 20, the mass of the primary particles 112, the mass of the anchoring groups 1151 and the mass of the polymer segments 1152 are all within a reasonable range. On the one hand, the anchoring groups 1151 and the polymer segments 1152 cooperate with each other to improve the dispersion performance of the composite lithium supplement material 100. On the other hand, it is possible to avoid excessive mass content of the anchoring groups 1151 and the polymer segments 1152 and reduce the mass proportion of the primary particles 112, so that the composite lithium supplement material 100 has a higher energy density.
[0123] Optionally, in the second embodiment of the present application, a coating layer 140 is provided on the periphery of the secondary particle 110, and the coating layer 140 includes a modified layer 120 and an ion-conducting layer 130. The structures of the modified layer 120 and the ion-conducting layer 130 are as described above and will not be repeated here.
[0124] See also Figure 4 In some embodiments, the preparation method comprises:
[0125] S101 , providing functional additives and primary particles 112 , wherein the primary particles 112 are lithium-rich particles, and the functional additives include one or more of a conductive agent, a dispersant 115 and a catalyst.
[0126] Optionally, in some embodiments, the functional additive includes a conductive agent; in other embodiments, the functional additive includes a dispersant 115 and a catalyst.
[0127] Optionally, the primary particles 112 are lithium-rich particles, and the lithium-rich particles can be selected from at least one of ternary lithium-rich compounds, binary lithium-rich compounds, and organic lithium salts. The specific compounds and chemical formulas are detailed above and will not be repeated here.
[0128] In one embodiment, when the primary particles 112 are ternary lithium-rich compounds, the preparation process of the lithium-rich particles includes: mixing a lithium source and other metal sources, calcining at 780° C. for 8 hours under an inert atmosphere, and then ball milling to obtain lithium-rich particles, wherein the lithium-rich particles are relatively small in size and are primary particles 112.
[0129] S102 , mixing and dispersing the functional additive with the primary particles 112 , so that at least a portion of the functional additive is distributed among the plurality of primary particles 112 , to obtain secondary particles 110 .
[0130] It can be understood that the secondary particles 110 are composed of a plurality of primary particles 112 and functional additives, and at least part of the functional additives are distributed among the plurality of primary particles 112 .
[0131] Optionally, when the functional additive includes a conductive agent and the conductive agent is cellulose nanocrystals 113, the cellulose nanocrystals 113 are mixed with primary particles 112 and calcined to obtain the secondary particles 110; wherein the secondary particles 110 include a plurality of secondary particles 110, the secondary particles 110 are composited by a plurality of primary particles 112 and a functional additive, the functional additive is cellulose nanocrystals 113, and the cellulose nanocrystals 113 shuttle in the gaps between the plurality of primary particles 112 to form a conductive network.
[0132] Optionally, when the functional additive includes a catalyst and a dispersant 115, the catalyst is dispersed and mixed with the primary particles 112, and then the dispersant 115 is added to obtain the secondary particles 110, wherein the secondary particles 110 include a plurality of secondary particles 110, the secondary particles 110 are composited with a plurality of primary particles 112 and the functional additive, the catalyst is in granular form, and the catalyst is filled in the gaps between the plurality of primary particles 112.
[0133] In the composite lithium-replenishing material 100 provided in this embodiment, the composite lithium-replenishing material 100 includes a plurality of secondary particles 110, and each secondary particle 110 includes a plurality of primary particles 112 and a functional additive composite, at least part of the functional additive is distributed between the plurality of primary particles 112, and the functional additive is selected from one or more of a conductive agent, a dispersant 115 and a catalyst. When the composite lithium supplement material 100 includes a plurality of secondary particles 110, and the secondary particles 110 are formed by a plurality of primary particles 112 and cellulose nanocrystals 113, the cellulose nanocrystals 113 have good electronic conductivity and ionic conductivity. When the cellulose nanocrystals 113 are arranged in the secondary particles 110, the cellulose nanocrystals 113 establish an electron transmission network in the secondary particles 110 to form a conductive network, and construct an ion transmission network to increase the rate at which the lithium ions move in the cellulose nanocrystals 113, so that the lithium ions of the primary particles 112 can escape from the composite lithium supplement material 100 and move to the electrolyte, and finally replenish lithium on the negative electrode side, so that the composite lithium supplement material 100 has good conductivity and lithium supplement performance.
[0134] When the composite lithium supplement material 100 includes a plurality of secondary particles 110, and the secondary particles 110 are formed by a plurality of primary particles 112, the dispersant 115, and the catalyst, the dispersant 115 can significantly improve the dispersion performance of the composite lithium supplement material 100, and the catalyst can improve the electrical conductivity and ion conductivity of the composite lithium supplement material 100, so as to reduce the impedance of lithium ions moving in the composite lithium supplement material 100, and improve the rate at which the lithium ions move in the cellulose nanocrystals 113, so that the lithium ions of the primary particles 112 can escape from the composite lithium supplement material 100 and move to the electrolyte, and finally replenish lithium on the negative electrode side, so that the composite lithium supplement material 100 has good electrical conductivity and lithium replenishment performance.
[0135] Optionally, the preparation method of the composite lithium-replenishing material further includes: forming a coating layer 140 on the surface of the secondary particle 110 to obtain the composite lithium-replenishing material 100, wherein the coating layer 140 includes an acid-base complex containing lithium and / or an ion-conducting material.
[0136] It can be understood that the composite lithium supplement material 100 includes secondary particles 110 and a coating layer 140 , and the coating layer 140 is coated on the outer periphery of the secondary particles 110 .
[0137] It can be understood that when the coating layer 140 includes an acid-base complex containing lithium, the acid-base complex containing lithium forms a modified layer 120 on the periphery of the secondary particle 110 , and the coating layer 140 includes the modified layer 120 .
[0138] It can be understood that when the coating layer 140 includes an ion-conducting material, the ion-conducting material forms the ion-conducting layer 130 on the periphery of the secondary particle 110, and the coating layer 140 includes the ion-conducting layer 130.
[0139] Optionally, the secondary particles 110 are modified by Lewis acid and / or anchoring groups 1151 to remove residual alkali on the surface of the primary particles 112 , and reactants generated during the modification process include acid-base complexes containing lithium to form the modified layer 120 .
[0140] In the preparation method of the composite lithium supplement material 100 provided in this embodiment, a modified layer 120 is formed on the surface of the secondary particle 110 to remove the residual alkali on the surface of the primary particle 112 and form a coating layer on the periphery of the secondary particle 110. The composite lithium supplement material 100 prepared by the preparation method provided in this embodiment can avoid the formation of gel-like substances on the surface or inside of the positive electrode, avoid increasing the transmission path of lithium ions and increase the coating difficulty of the composite lithium supplement material 100, and can also avoid the residual alkali and the electrolyte from having a side reaction, thereby improving the lithium supplement performance, processing performance and safety performance of the composite lithium supplement material 100. In addition, the modified layer 120 can also prevent the electrolyte from directly contacting the primary particle 112 and increase the service life of the composite lithium supplement material 100. Furthermore, the modified layer 120 includes an acid-base complex containing lithium. When the composite lithium supplement material 100 is applied to a secondary battery and during the charge and discharge process of the secondary battery, the modified layer 120 facilitates the insertion and removal of lithium ions, which can further improve the lithium supplement performance of the composite lithium supplement material 100. The composite lithium supplement material 100 obtained in this embodiment has good electrical conductivity and ion conductivity, and the primary particles 112 contain less or no residual alkali, so that the composite lithium supplement material 100 has good coating performance and use performance. The ion conductive layer 130 is equivalent to setting another coating layer on the periphery of the modified layer 120 to prevent the modified layer 120 from rupturing and causing other substances in the electrolyte to directly contact the primary particles 112. The ion conductive layer 130 acts as a buffer layer between the secondary particles 110 and the electrolyte. When the composite lithium supplement material 100 is applied to a secondary battery, it is beneficial to stabilize the interface structure between the positive electrode and the electrolyte, thereby reducing the side reaction between the electrolyte and the composite lithium supplement material 100 and improving the cycle stability of the secondary battery.
[0141] Optionally, the process of mixing the cellulose nanocrystal 113 precursor with the primary particles 112 and calcining them to obtain the secondary particles 110 includes: ultrasonically dispersing the primary particles 112 and the cellulose nanocrystals 113 in anhydrous ethanol, then drying, and calcining at 300°C for 5 hours to obtain the secondary particles 110, wherein the secondary particles 110 construct a conductive network with cellulose nanocrystals 113, the primary particles 112 are lithium-rich particles and a plurality of lithium-rich particles are agglomerated, and the cellulose nanocrystals 113 are dispersed on the surface of the primary particles 112 or between a plurality of the primary particles 112.
[0142] It can be understood that dispersing the lithium-rich material and the cellulose nanocrystals 113 by using liquid anhydrous ethanol is beneficial to making the primary particles 112 and the cellulose nanocrystals 113 dispersed more evenly, so that the primary particles 112 are evenly distributed on the cellulose nanocrystals 113 .
[0143] In the first embodiment, the coating layer 140 is formed on the surface of the secondary particle 110 and the coating layer 140 includes a modified layer 120, which includes: at a preset temperature, the secondary particle 110 is modified with lithium hexafluorophosphate to form a modified layer 120 on the surface of the secondary particle 110, and the preset temperature T satisfies the range: 165℃≤T≤200℃.
[0144] Specifically, the value of the preset temperature T may be, but is not limited to, 165°C, 168°C, 170°C, 175°C, 178°C, 180°C, 185°C, 188°C, 190°C, 192°C, 195°C, 198°C and 200°C, etc.
[0145] It can be understood that at the preset temperature, the lithium hexafluorophosphate decomposes to generate lithium fluoride and phosphorus pentafluoride, and the reaction formula is LiPF6=PF5+LiF.
[0146] It can be understood that the modified layer is composed of an acid-base complex containing lithium generated by the reaction of phosphorus pentafluoride with lithium hydroxide, lithium carbonate, etc.
[0147] In this embodiment, lithium hexafluorophosphate is used to modify the secondary particles 110 at a preset temperature, wherein the lithium hexafluorophosphate decomposes at the preset temperature to generate gaseous phosphorus pentafluoride, the gaseous phosphorus pentafluoride volatilizes to the secondary particles 110, and reacts with the residual alkali of the primary particles 112 on the secondary particles 110 to neutralize the primary particles 112 on the secondary particles 110, so as to remove the alkali of the primary particles 112 on the secondary particles 110, and form a modified layer 120 on the surface of the secondary particles 110. When the preset temperature T satisfies the range of 165°C≤T≤200°C, lithium hexafluorophosphate can decompose to generate phosphorus pentafluoride, and the phosphorus pentafluoride reacts with lithium hydroxide, lithium carbonate, etc. at the preset temperature to generate an acid-base complex containing lithium, the acid-base complex is stably arranged on the periphery of the secondary particles 110 and forms the modified layer 120, so that the residual alkali content in the primary particles 112 is less or almost absent, thereby improving the coating performance and use performance of the composite lithium supplement material 100.
[0148] It can be understood that the process of modifying the secondary particles 110 with phosphorus pentafluoride includes: first, the Lewis acid gas phosphorus pentafluoride first reacts with the residual alkali such as lithium hydroxide, lithium carbonate, etc. on the surface of the primary particles 112 to remove the residual alkali on the surface of the primary particles 112 of the secondary particles 110. Further, phosphorus pentafluoride reacts with the surface structure of the primary particles 112, so that fluoride ions are doped into the surface structure of the primary particles 112, and an amorphous phosphide coating layer is formed on the surface of the primary particles 112 to improve the transmission capacity of the primary particles 112 for lithium ions. In addition, during the charge and discharge cycle of the secondary battery, the phosphide coating layer can also inhibit the release of oxygen generated by the primary particles 112, slowing down the gas production of the secondary battery during the charge and discharge process, and the phosphide coating layer can also remove impurities on the surface of the primary particles 112, improving the processing performance of the primary particles 112.
[0149] Optionally, the lithium hexafluorophosphate modifies the secondary particles 110 by a hydrothermal reaction.
[0150] Specifically, the secondary particles 110 prepared by S102 are placed in a polytetrafluoroethylene bushing, lithium hexafluorophosphate is placed in another polytetrafluoroethylene bushing, and then the two are placed in a large bushing. The bushing is then placed in a hydrothermal reactor and reacted at 180°C for 12 hours. The lithium hexafluorophosphate decomposes to generate phosphorus pentafluoride, which modifies the secondary particles 110 to form a modified layer 120 on the surface of the secondary particles 110.
[0151] Optionally, the providing of functional additives and primary particles 112, wherein the functional additives include a catalyst, comprises: ammonium molybdate (H 24 Mo7N6O 24·4H2O) and nickel nitrate and thiourea are placed in a hydrothermal reactor in a certain proportion, and graphene oxide, reducing sugars (such as glucose) and amino compounds (such as amino acids and proteins) are added at the same time, and the hydrothermal reaction is controlled to be 180°C. Ammonium molybdate, nickel nitrate and thiourea react to form a metal compound layer 1141, and the metal compound layer 1141 is arranged on the surface of the graphene, and the reducing sugars and amino compounds form an intercalation layer 1142 to be inserted between two adjacent metal compound layers 1141, and the intercalation layer 1142 is nitrogen-doped amorphous carbon. After hydrothermal, the solid powder is placed in an inert gas and annealed at 800°C to enhance carbonization and improve crystallinity.
[0152] It can be understood that the catalyst is a superlattice catalyst 114, and the superlattice catalyst 114 includes a metal compound layer 1141, an intercalation layer 1142 and graphene. The metal compound layer 1141 and the intercalation layer 1142 both extend along a first direction, and the metal compound layer 1141 and the intercalation layer 1142 are alternately arranged along a second direction, and the metal compound layer 1141 and the intercalation layer 1142 are arranged on the surface of the graphene.
[0153] Optionally, the mixing and dispersing of the functional catalyst with the primary particles 112 so that at least part of the functional additive is distributed among the plurality of primary particles 112 to obtain the secondary particles 110 includes:
[0154] The catalyst and the catalyst are ultrasonically dispersed in nitrogen-methyl pyrrolidone, and the anchoring group 1151 and the chain structure are added after complete dispersion. After further ultrasonic dispersion, they are evenly dispersed and filtered to obtain solid particles. The solid particles are dried at low temperature to obtain the composite lithium supplement material 100, wherein the catalyst is granular and filled in the gaps between the multiple primary particles 112, the multiple anchoring groups 1151 are arranged at intervals on the surface of the primary particles 112, one end of the polymer segment 1152 is connected to the anchoring group 1151, and the other end of the polymer segment 1152 extends in a direction away from the primary particle 112, and the anchoring group 1151 modifies the secondary particle 110 to form a modified layer 120 on the surface of the secondary particle 110.
[0155] Optionally, the anchoring group 1151 is selected from at least one of -COOH, Ar-OH and -SO3H
[0156] Optionally, the chain structure is selected from at least one of polyolefin, polyester, polyacrylate and polyether.
[0157] In some embodiments, the preparation method further comprises: when the coating layer 140 comprises an acid-base complex containing lithium and an ion-conducting material, firstly forming an acid-base complex containing lithium on the periphery of the secondary particle 110 and forming a modified layer 120, and then depositing an ion-conducting layer 130 on the surface of the modified layer 120, wherein the ion conductivity σ of the ion-conducting layer 130 satisfies the range: 10 -8 S / cm≤σ≤10 -2 S / cm.
[0158] The composite lithium supplement material 100 obtained by the preparation method provided in this embodiment includes secondary particles 110, a modified layer 120 and an ion-conducting layer 130, and the secondary particles 110, the modified layer 120 and the ion-conducting layer 130 are arranged in sequence from the inside to the outside. The ion-conducting layer 130 is equivalent to arranging another coating layer on the periphery of the modified layer 120 to prevent the modified layer 120 from rupturing and causing other substances in the electrolyte to directly contact the primary particles 112. The ion-conducting layer 130 acts as a buffer layer between the secondary particles 110 and the electrolyte. When the composite lithium supplement material 100 is applied to a secondary battery, it is beneficial to stabilize the interface structure between the positive electrode and the electrolyte, thereby reducing the side reaction between the electrolyte and the composite lithium supplement material 100 and improving the cycle stability of the secondary battery. In addition, the ionic conductivity σ of the ion-conducting layer 130 satisfies the range: 10 -8 S / cm≤σ≤10 -2 S / cm, the ion-conducting layer 130 has good ion-conducting performance, which facilitates the lithium ions to enter the cellulose nanocrystals 113 from the electrolyte, and also facilitates the lithium ions of the primary particles 112 to escape and be transferred from the cellulose nanocrystals 113 to the electrolyte. The ion-conducting layer 130 is beneficial to reducing the interface impedance between the positive electrode and the electrolyte, thereby helping to improve the charge and discharge efficiency of the secondary battery and extend the service life of the secondary battery.
[0159] Optionally, depositing the ion-conducting layer 130 on the surface of the modified layer 120 includes: depositing the ion-conducting layer 130 on the surface of the modified layer 120 using an atomic deposition method to improve the bonding performance between the modified layer 120 and the ion-conducting layer 130, and making the ion-conducting layer 130 thinner and easier to transport lithium ions.
[0160] In a specific embodiment, the ion-conducting layer 130 is deposited on the surface of the modified layer 120 by an atomic deposition method, including: placing the composite lithium-supplementing material 100 of the secondary particles 110 coated with the modified layer 120 in an atomic layer deposition device, controlling the chamber temperature to 250°C, and alternately introducing a niobium source and a lithium source into the atomic layer deposition device to deposit the ion-conducting layer 130 on the surface of the modified layer 120, wherein the ion-conducting layer 130 includes LiNbO3.
[0161] It is understandable that if the niobium source and the lithium source are introduced at the same time, the niobium source and the lithium source react in the air, and the reactants are difficult to be deposited on the surface of the modified layer 120 .
[0162] Among them, the niobium source is selected from Nb(Et)5, and the lithium source is LiO t Bu. The two are alternately introduced into the atomic layer deposition device to make the niobium source and the lithium source react on the surface of the modified layer 120 and form LiNbO3 on the surface of the modified layer 120. Lithium ions have a high transmission efficiency in the ion-conducting layer 130. Among them, Nb(Et)5 is pentaethyl niobium, which is an organic niobium compound composed of niobium atoms and five ethyl groups bonded by chemical bonds; LiO t Bu is lithium tert-butoxide, which is an alkali metal oxide, and its chemical formula may also be (CH3)3COLi.
[0163] The present application also provides a positive electrode material, which includes a positive electrode active material and a composite lithium supplement material 100. The composite lithium supplement material 100 includes the composite lithium supplement material 100 provided in the present application, or includes the composite lithium supplement material 100 obtained by the preparation method of the composite lithium supplement material 100 provided in the present application.
[0164] In this embodiment, the positive electrode material includes a positive electrode active material and a composite lithium supplement material 100. The composite lithium supplement material 100 provided in this application and the composite lithium supplement material 100 obtained by the preparation method of the composite lithium supplement material 100 provided in this application have electrical conductivity and ion conductivity, and the primary particles 112 contain less or no residual alkali, so that the composite lithium supplement material 100 has good coating performance and use performance. When the composite lithium supplement material 100 is applied to the positive electrode material, the positive electrode material has good use performance, lithium supplement performance and coating performance.
[0165] The present application also provides a secondary battery, the secondary battery comprising a negative electrode, a positive electrode and an electrolyte, wherein the positive electrode comprises the above-mentioned composite lithium supplement material or the above-mentioned positive electrode material; the electrolyte may be an electrolyte, in which case the secondary battery further comprises a diaphragm disposed between the positive electrode and the negative electrode; or the electrolyte may be a solid electrolyte, in which case the diaphragm is not disposed in the secondary battery and is replaced by a solid electrolyte. Optionally, the electrolyte comprises a solvent and an electrolyte, the solvent is used to dissolve the electrolyte, and part of the solvent may enter the cellulose nanocrystal 113 from the ion-conducting layer 130 and the modified layer 120, and contact the primary particles 112.
[0166] It can be understood that the secondary battery is a lithium-ion battery.
[0167] In this embodiment, the positive electrode includes the positive electrode material provided in this application. In the process of preparing the positive electrode, the primary particles 112 of the composite lithium supplement material 100 contain less or no residual alkali, which can avoid the formation of gel-like substances on the surface or inside of the positive electrode, avoid increasing the transmission path of lithium ions and increase the difficulty of coating the composite lithium supplement material 100, and avoid the side reaction of residual alkali with the electrolyte, so that the composite lithium supplement material 100 has good lithium supplement performance, processing performance and safety performance. Further, during the charge and discharge process of the secondary battery, the composite lithium supplement material 100 in the positive electrode material has good electrical conductivity and ion conductivity, which facilitates the composite lithium supplement material 100 to release lithium ions and replenish them to the negative electrode side to replenish the lithium ions consumed in the secondary battery, so that the secondary battery has a higher energy density and better cycle performance.
[0168] The technical solution of the present invention is further described below in multiple embodiments:
[0169] Example 1 to Example 11, Comparative Example 1 to Comparative Example 7:
[0170] Example 1 to Example 6, Comparative Example 1 to Comparative Example 4:
[0171] The present embodiment provides a composite lithium supplement material 100, the composite lithium supplement material 100 includes a plurality of secondary particles 110, each of the secondary particles 110 is composited by a plurality of primary particles 112 and functional additives, at least part of the functional additives are distributed between the plurality of primary particles 112, the primary particles 112 are lithium-rich particles, the functional additives are selected from one or more of a conductive agent, a dispersant 115 and a catalyst, the modified layer 120 is coated on the periphery of the secondary particles 110, the modified layer 120 includes an acid-base complex containing lithium, and the ion conductivity σ of the ion conductive layer 130 satisfies the range: 10 - 8 S / cm≤σ≤10 -2 S / cm.
[0172] Wherein, in Examples 1 to 6 and Comparative Examples 1 to 4, the functional additive is a conductive agent, and the conductive agent includes cellulose nanocrystals 113, and the cellulose nanocrystals 113 shuttle between the gaps of multiple primary particles 112 to form a conductive network. Wherein, in the secondary particles 110, the mass ratio of the cellulose nanocrystals 113 to the primary particles 112 is 1:20; wherein the cellulose nanocrystals 113 are one-dimensional materials, and the chemical formula of the primary particles 112 is Li2NiO2, wherein the diameter D of the one-dimensional material, the length L of the one-dimensional material, and the particle size D' of the secondary particles 110 are shown in Table 1.
[0173] In the modified layer 120 , the modified layer 120 includes Li 3 PO 4 , and a thickness d2 of the modified layer 120 is as shown in Table 1.
[0174] In the ion conductive layer 130 , the ion conductive layer 130 includes LiNbO 3 , and a thickness d1 of the ion conductive layer 130 is as shown in Table 1.
[0175] The preparation method of the composite lithium supplement material 100 of Examples 1 to 6 and Comparative Examples 1 to 4 comprises the following steps:
[0176] 1) Lithium hydroxide and nickel oxide are mixed in a molar ratio of 2:1, calcined at 780° C. for 8 h in a nitrogen atmosphere, and then ball-milled to obtain lithium-rich particles. The lithium-rich particles are small in size and are primary particles 112. The structural formula of the primary particles 112 is Li2NiO2.
[0177] 2) The lithium-rich material and cellulose nanocrystals 113 are ultrasonically dispersed in anhydrous ethanol, then dried, and calcined at 300° C. for 5 h to obtain the secondary particles 110, wherein the secondary particles 110 construct a conductive network with cellulose nanocrystals 113, and the cellulose nanocrystals 113 are dispersed on the surfaces of the multiple primary particles 112.
[0178] 3) At a preset temperature, the secondary particles 110 are modified with lithium hexafluorophosphate to form a modified layer 120 on the surface of the secondary particles 110 , wherein the preset temperature T satisfies the range of 165° C. ≤ T ≤ 200° C.
[0179] 4) Depositing the ion-conducting layer 130 on the surface of the modified layer 120 by an atomic deposition method.
[0180] Table 1 below lists the parameters of the composite lithium supplementing materials 100 of Examples 1 to 6 and Comparative Examples 1 to 4.
[0181] Table 1: Parameters of the composite lithium supplementing materials 100 of Examples 1 to 6 and Comparative Examples 1 to 4:
[0182]
[0183]
[0184] It can be understood that no functional additives are added to the composite lithium supplement material 100 of Comparative Example 1, that is, no cellulose nanocrystals 113, superlattice catalysts 114 and dispersants 115 are added to Comparative Example 1.
[0185] Example 7 to Example 11, Comparative Example 5 to Comparative Example 7:
[0186] Among them, in Examples 7 to 10 and Comparative Examples 5 to 7, the functional additives are dispersants 115 and catalysts, the catalyst is a superlattice catalyst 114, the dispersant 115 includes a plurality of anchoring groups 1151 and a plurality of polymer segments 1152, the plurality of anchoring groups 1151 are arranged at intervals on the surface of the primary particle 112, one end of the polymer segment 1152 is connected to the anchoring group 1151, and the other end of the polymer segment 1152 extends in a direction away from the primary particle 112. Among them, in the secondary particle 110, the mass fraction of the superlattice catalyst 114, the particle size d3 of the superlattice catalyst 114, the mass fraction of the dispersant 115 and the particle size D' of the secondary particle 110 are shown in Table 2.
[0187] It can be understood that the mass fraction of the superlattice catalyst 114 is the ratio of the mass of the superlattice catalyst 114 to the mass of the secondary particles 110 ; the mass fraction of the dispersant 115 is the ratio of the mass of the dispersant 115 to the mass of the secondary particles 110 .
[0188] In the modified layer 120 , the modified layer 120 includes Li 3 PO 4 , and in the ion conductive layer 130 , the ion conductive layer 130 includes LiNbO 3 . The thickness d1 of the ion conductive layer 130 is as shown in Table 2.
[0189] The preparation method of the composite lithium supplement material 100 of Examples 7 to 11 and Comparative Examples 5 to 7 comprises the following steps:
[0190] 1) Preparation of superlattice catalyst 114: Ammonium molybdate (H 24 Mo7N6O 24 ·4H2O) and nickel nitrate and thiourea are placed in a hydrothermal reactor in a certain proportion, and graphene oxide, reducing sugars (such as glucose) and amino compounds (such as amino acids and proteins) are added at the same time, and the hydrothermal reaction is controlled to be 180°C. Ammonium molybdate, nickel nitrate and thiourea react to form a metal compound layer 1141, and the metal compound layer 1141 is arranged on the surface of the graphene, and the reducing sugars and amino compounds form an intercalation layer 1142 to be inserted between two adjacent metal compound layers 1141, and the intercalation layer 1142 is nitrogen-doped amorphous carbon. After hydrothermal, the solid powder is placed in an inert gas and annealed at 800°C to enhance carbonization and improve crystallinity.
[0191] 2) Preparation of primary particles: lithium hydroxide and nickel oxide are mixed in a molar ratio of 2:1, calcined at 780°C for 8 hours under a nitrogen atmosphere, and then ball-milled to obtain lithium-rich particles. The lithium-rich particles are relatively small in size and are primary particles 112. The structural formula of the primary particles 112 is Li2NiO2.
[0192] 3) placing the catalyst and the catalyst in nitrogen-methyl pyrrolidone for ultrasonic dispersion, adding the anchoring group 1151 and the polymer segment 1152 after complete dispersion, further ultrasonically dispersing and filtering to obtain solid particles, and drying the solid particles at low temperature to obtain the composite lithium supplement material 100, wherein the superlattice catalyst 114 is granular and filled in the gaps between the multiple primary particles 112, the multiple anchoring groups 1151 are arranged at intervals on the surface of the primary particles 112, one end of the polymer segment 1152 is connected to the anchoring group 1151, and the other end of the polymer segment 1152 extends in a direction away from the primary particle 112, and the anchoring group 1151 modifies the secondary particle 110 to form a modified layer 120 on the surface of the secondary particle 110.
[0193] 4) Depositing the ion-conducting layer 130 on the surface of the modified layer 120 by an atomic deposition method.
[0194] Table 2 below lists the parameters of the composite lithium supplementing materials 100 of Examples 7 to 11 and Comparative Examples 5 to 7.
[0195] Table 2: Parameters of the composite lithium supplementing materials 100 of Examples 7 to 11 and Comparative Examples 5 to 7:
[0196]
[0197] It can be understood that the composite lithium supplement material 100 of comparative example 5 does not include the superlattice catalyst 114 , the composite lithium supplement material 100 of comparative example 6 does not include the dispersant 115 , and the composite lithium supplement material 100 of comparative example 7 does not include the ion conductive layer 130 .
[0198] The composite lithium supplement materials 100 provided in the above-mentioned Examples 1 to 11 and Comparative Examples 1 to 7 are respectively assembled into positive electrodes and secondary batteries according to the following methods:
[0199] Positive electrode: The composite lithium supplement material 100, SP (conductive carbon black) and PVDF (polyvinylidene fluoride) were mixed in a mass ratio of 90:4:6 to prepare a positive electrode slurry, the positive electrode slurry was coated on the surface of aluminum foil, vacuum dried at 110°C overnight, and rolled to obtain a positive electrode;
[0200] Negative electrode: lithium sheet;
[0201] Electrolyte: Ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7, and LiPF6 was added to form an electrolyte, and the concentration of LiPF6 was 1 mol / L;
[0202] Diaphragm: polypropylene microporous diaphragm;
[0203] Secondary battery assembly: Assemble button-type lithium-ion full batteries in an inert atmosphere glove box in the order of negative electrode-diaphragm-electrolyte-positive electrode.
[0204] The secondary batteries assembled in the above embodiments and comparative examples were subjected to electrochemical performance tests under the following test conditions:
[0205] The charge rate is 0.1C, and the cut-off voltage is set to 4.1V or 4.3V; the constant voltage charge is performed at 4.1V or 4.3V; after the charging process is completed, the battery is allowed to stand for 10 minutes and then discharged at a rate of 0.1C with a cut-off voltage of 2.5V; the charging platform is observed during the charging process to obtain the delithiation voltage of the composite lithium supplement material 100.
[0206] The test results of the composite lithium supplement material 100 and the secondary battery are shown in Table 3 below:
[0207] Table 3: Test results of Examples 1 to 11 and Comparative Examples 1 to 7:
[0208]
[0209] Please refer to Table 1 and Table 3. It can be seen from the data of Examples 1 to 6 and Comparative Example 1 that the delithiation voltage of the composite lithium supplement material 100 of Examples 1 to 6 is lower than the delithiation voltage of the composite lithium supplement material 100 of Comparative Example 1, and the charging capacity of the secondary battery of Examples 1 to 6 at a cut-off voltage of 4.1V is higher than the charging capacity of the secondary battery of Comparative Example 1 at a cut-off voltage of 4.1V, and the charging capacity of the secondary battery of Examples 1 to 6 at a cut-off voltage of 4.3V is higher than the charging capacity of the secondary battery of Comparative Example 1 at a cut-off voltage of 4.3V. This is because: the composite lithium supplement material 100 in Comparative Example 1 does not include a conductive agent. In Examples 1 to 6, the conductive agent includes cellulose nanocrystals 113, and the cellulose nanocrystals 113 have good electronic conductivity and ionic conductivity. The cellulose nanocrystals 113 establish an electronic transmission network in the secondary particles 110 to form a conductive network, and construct an ion transmission network, which is beneficial to shorten the transmission path of lithium ions passing through the primary particles 112, thereby increasing the rate at which the lithium ions move in the secondary particles 110, so that the composite lithium supplement material 100 of Examples 1 to 6 has a lower delithiation voltage, and the secondary batteries of Examples 1 to 6 have a higher charge specific capacity when the cut-off voltage is 4.1V and 4.3V.
[0210] Specifically, referring to Example 1, Example 2 and Comparative Example 2, the diameter D of the one-dimensional material of Example 1 and Example 2 satisfies the range of 5nm≤D<200nm, and the diameter of the one-dimensional material of Comparative Example 2 is 200nm. Then, as the diameter D of the one-dimensional material increases, the delithiation voltage of the composite lithium supplement material 100 first decreases and then increases, and the charging specific capacity when the cut-off voltage is 4.1V and the charging specific capacity when the cut-off voltage is 4.3V first increase and then decrease. This shows that the conductive properties of the composite lithium supplement material 100 will be affected when the diameter of the one-dimensional material is too large or too small. This is because: when the diameter of the one-dimensional material is too small, the one-dimensional material is too fine, which may reduce the structural stability of the cellulose nanocrystals 113 formed by the one-dimensional material, and the cellulose nanocrystals 113 cannot be well inserted into the gaps of the primary particles 112, and the binding performance of the cellulose nanocrystals 113 and the primary particles 112 is poor. During the charge and discharge process of the secondary battery, the conductive network formed by the cellulose nanocrystals 113 may be broken or agglomerated, thereby affecting the stability of the conductive network formed by the cellulose nanocrystals 113. When the diameter of the one-dimensional material is too large, the cellulose nanocrystals 113 with too large a diameter have too small a specific surface area, which reduces the contact area and permeation channels between the cellulose nanocrystals 113 and the solvent in the electrolyte, reduces the efficiency of lithium ion transmission between the cellulose nanocrystals 113 and the electrolyte, is not conducive to the transmission of lithium ions, and thus reduces the charging capacity of the secondary battery.
[0211] Specifically, referring to Example 1 and Example 3, the length L of the one-dimensional material satisfies 20nm≤L≤1000nm, and as the length L of the one-dimensional material increases, the delithiation voltage of the composite lithium supplement material 100 increases, and the charge specific capacity when the cut-off voltage is 4.1V and the charge specific capacity when the cut-off voltage is 4.3V decrease. This is because: as the length L of the one-dimensional material increases, the internal resistance of the cellulose nanocrystal 113 may increase, reducing the efficiency of electron and lithium ion transmission between the cellulose nanocrystal 113 and the electrolyte, and the one-dimensional material that is too long is easy to break and cannot be well inserted in the gap of the primary particle 112, so that the binding performance between the one-dimensional material and the primary particle 112 is poor, and the structural stability of the conductive network formed by the accumulation of the one-dimensional material is reduced, so that the delithiation potential of the composite lithium supplement material 100 of Example 3 is higher, and the charge specific capacity when the cut-off voltage is 4.1V and the charge specific capacity when the cut-off voltage is 4.3V are smaller.
[0212] Specifically, referring to Example 1 and Example 4, the particle size D' of the secondary particles 110 all satisfies the range of 0.3μm≤D'≤500μm, and as the particle size of the secondary particles 110 increases, the delithiation voltage of the composite lithium supplement material 100 increases, and the charging capacity when the cut-off voltage is 4.1V and the charging capacity when the cut-off voltage is 4.3V decrease. This is because: as the particle size of the secondary particles 110 increases, during the charge and discharge process, the diffusion path of the lithium ions in the secondary particles 110 is The longer it is, the greater the resistance to the deintercalation of lithium ions from the secondary particles 110, which reduces the efficiency of the lithium ions of the secondary particles 110 being sequentially deintercalated from the secondary particles 110 and the modified layer 120 into the electrolyte and embedded into the negative electrode side, thereby reducing the lithium replenishment performance of the composite lithium replenishing material 100, so that the delithiation potential of the composite lithium replenishing material 100 of Example 4 is higher, and the charging specific capacity when the cut-off voltage is 4.1V and the charging specific capacity when the cut-off voltage is 4.3V are smaller.
[0213] Specifically, referring to Example 1, Example 5 and Comparative Example 3, the thickness d2 of the modified layer 120 in Example 1 and Example 5 satisfies the range of 0.01nm≤d2≤5nm, but the composite lithium supplement material 100 of Comparative Example 3 does not include the modified layer 120, which makes the delithiation voltage of the composite lithium supplement material 100 of Example 1 and Example 5 lower than the delithiation voltage of the composite lithium supplement material 100 of Comparative Example 3, and the charging specific capacity of the secondary battery of Example 1 and Example 5 at a cut-off voltage of 4.1V is higher than the charging specific capacity of the secondary battery of Comparative Example 3 at a cut-off voltage of 4.1V, and the charging specific capacity of the secondary battery of Example 1 and Example 5 at a cut-off voltage of 4.3V is higher than the charging specific capacity of the secondary battery of Comparative Example 3 at a cut-off voltage of 4. 3V charging capacity, and the secondary battery of comparative example 3 has gel in the preparation process. In addition, the performance of the composite lithium supplement material 100 of embodiment 1 is better than that of the composite lithium supplement material 100 of embodiment 5. This is because: the modified layer 120 is formed by the Lewis acid gas or the acidic anchoring group 1151 modifying the secondary particles 110 and accumulating the reactants generated in the modification process. The modified layer 120 is within a reasonable range. In the process of Lewis acid gas modifying the secondary particles 110, the Lewis acid gas and / or the acidic anchoring group 1151 can fully remove the residual alkali of the primary particles 112, so that the composite lithium supplement material 100 has good physical and chemical properties. The composite lithium supplement material 100 in comparative example 3 does not have a modified layer 120. When the composite lithium supplement material 100 is coated on the positive electrode and applied to the secondary battery, the residual alkali content in the composite lithium supplement material 100 is too high, which increases the coating difficulty of the composite lithium supplement material 100. Furthermore, as the thickness of the modified layer 120 increases, it indicates that the Lewis acid gas or the acidic anchoring group 1151 corrodes the secondary particle 110 excessively, which may affect the lithium replenishment performance of the primary particle 112. In addition, when the composite lithium replenishment material 100 is applied to a secondary battery, the thicker the modified layer 120 is, the greater the resistance of the lithium ions in the primary particle 112 to pass through the modified layer 120, which is not conducive to the lithium ions from the cellulose nanocrystals 113 passing through the modified layer 120, and then passing through the electrolyte to the negative electrode side for lithium replenishment, thereby reducing the transmission efficiency of lithium ions.
[0214] Specifically, referring to Example 1, Example 6 and Comparative Example 4, the thickness d1 of the ion conductive layer 130 of Example 1, Example 6 and Comparative Example 4 all satisfies the range of 0.5nm≤d1≤50nm, and as the thickness of the ion conductive layer 130 increases, the delithiation voltage of the composite lithium supplement material 100 gradually increases, and the charging specific capacity when the cut-off voltage is 4.1V and the charging specific capacity when the cut-off voltage is 4.3V gradually decrease. This is because: as the thickness of the ion conductive layer 130 increases, the diffusion path of lithium ions increases, which affects the release and transmission of lithium ions by the composite lithium supplement material 100 during the lithium supplement process, and when the size of the composite lithium supplement material 100 is determined, if the thickness of the ion conductive layer 130 is too large, it may also lead to the reduction of the secondary particles 110, thereby leading to the reduction of the primary particles 112, reducing the energy density of the composite lithium supplement material 100, and ultimately increasing the delithiation voltage of the composite lithium supplement material 100, and reducing the capacity of the corresponding secondary battery.
[0215] Please refer to Table 2 and Table 3. It can be seen from the data of Examples 7 to 11 and Comparative Example 5 that the composite lithium supplement materials 100 of Examples 7 to 11 all include the superlattice catalyst 114, and the composite lithium supplement material 100 of Comparative Example 5 does not include the superlattice catalyst 114, which makes the delithiation voltage of the composite lithium supplement material 100 of Examples 7 to 11 lower than the delithiation voltage of the composite lithium supplement material 100 of Comparative Example 5, and the charging specific capacity of the secondary battery of Examples 7 to 11 at a cut-off voltage of 4.1V is higher than the charging specific capacity of the secondary battery of Comparative Example 5 at a cut-off voltage of 4.1V, and the charging specific capacity of the secondary battery of Examples 7 to 11 at a cut-off voltage of 4.3V is higher than that of the secondary battery of Comparative Example 5. The secondary battery of Ratio 5 has a high charging capacity when the cut-off voltage is 4.3V. This is because: the superlattice catalyst 114 constructs an ion-conducting network and a conductive network, which can significantly reduce the diffusion barrier of lithium ions in the secondary particles 110, so as to realize the rapid movement of lithium ions in the secondary particles 110, thereby facilitating the lithium ions of the primary particles 112 to escape from the composite lithium supplement material 100 and move to the electrolyte, and finally replenish lithium on the negative electrode side, so that the composite lithium supplement material 100 has good conductivity and lithium replenishment performance, so that the composite lithium supplement material 100 of Examples 7 to 11 has a lower lithium decomposition voltage, and Examples 7 to 11 also have a higher charging capacity when the cut-off voltage is low.
[0216] Specifically, please refer to Example 7 and Example 8, the mass fraction of the superlattice catalyst 114 satisfies the range of 4% to 10%, wherein, in the secondary particles 110, the mass fraction of the superlattice catalyst 114 is the ratio of the mass of the superlattice catalyst 114 to the mass of the secondary particles 110, and as the mass fraction of the superlattice catalyst 114 increases, the delithiation voltage of the composite lithium supplement material 100 decreases, but the corresponding secondary battery also decreases when the cut-off voltage is 4.1V and 4.3V. This is because: although the superlattice catalyst 114 can construct an ion-conducting network and a conductive network to reduce the diffusion barrier of lithium ions in the secondary particles 110, as the mass of the superlattice catalyst 114 increases, the mass proportion of the primary particles 112 in the secondary particles 110 is reduced, thereby causing the energy density of the composite lithium supplement material 100 to decrease, and then causing the corresponding secondary battery to decrease the charge specific capacity when the cut-off voltage is 4.1V and 4.3V. Therefore, preferably, the mass fraction of the superlattice catalyst 114 is 4% to 6%, and more preferably, the mass fraction of the superlattice catalyst 114 is 5%.
[0217] Specifically, referring to Example 7 and Example 11, the particle size d3 of the superlattice catalyst 114 satisfies the range of 50nm≤d3≤5000nm, and as the particle size of the superlattice catalyst 114 increases, the delithiation voltage of the composite lithium supplement material 100 gradually increases, and the charging specific capacity when the cut-off voltage is 4.1V and the charging specific capacity when the cut-off voltage is 4.3V gradually decrease. This is because: as the particle size of the superlattice catalyst 114 increases, the contact area between the superlattice catalyst 114 and the primary particles 112 decreases, making it difficult for the superlattice catalyst 114 to function, and ultimately making the composite lithium supplement material 100 of Example 7 have a lower delithiation voltage, and Example 7 also has a higher charging specific capacity when the cut-off voltage is low.
[0218] Specifically, please refer to Example 7, Example 9 and Comparative Example 6. The mass fraction of the dispersant 115 in the composite lithium supplement material 100 of Example 7 and Example 9 satisfies the range of 0.3% to 1.2%, wherein, in the secondary particles 110, the mass fraction of the dispersant 115 is the ratio of the mass of the dispersant 115 to the mass of the secondary particles 110, while the composite lithium supplement material 100 of Comparative Example 6 does not include the dispersant 115, which makes the delithiation decomposition voltage of the composite lithium supplement material 100 of Example 7 and Example 9 lower than the delithiation decomposition voltage of the composite lithium supplement material 100 of Comparative Example 6, and the charging specific capacity of the secondary battery of Example 7 and Example 9 at a cut-off voltage of 4.1V is higher than the charging specific capacity of the secondary battery of Comparative Example 6 at a cut-off voltage of 4.1V, and the secondary battery of Example 7 and Example 9 at a cut-off voltage of 4. The charging specific capacity at 3V is higher than the charging specific capacity of the secondary battery in comparative example 6 when the cut-off voltage is 4.3V. In addition, the physicochemical properties of the composite lithium supplement material 100 of Example 7 are better than the physicochemical properties of the composite lithium supplement material 100 of Example 9. This is because: the dispersant 115 can significantly improve the dispersibility of the composite lithium supplement material 100, and the catalyst can improve the conductivity and ion conductivity of the composite lithium supplement material 100, so as to reduce the impedance of the movement of lithium ions in the composite lithium supplement material 100, and increase the rate of movement of the lithium ions in the cellulose nanocrystals 113, so that the lithium ions of the primary particles 112 can escape from the composite lithium supplement material 100 and move to the electrolyte, and finally replenish lithium on the negative electrode side, so that the composite lithium supplement material 100 has good conductivity and lithium replenishment performance. However, when the mass fraction of the dispersant 115 reaches a certain level, further increasing the mass fraction of the dispersant 115 is difficult to improve the dispersion performance of the secondary particles 110, but instead reduces the mass proportion of the primary particles 112 in the secondary particles 110, which does not lead to an increase in the energy density of the composite lithium supplement material 100.
[0219] Specifically, referring to Example 7 and Example 10, the particle size D' of the secondary particle 110 satisfies the range of 0.3 μm ≤ D' ≤ 500 μm, and as the particle size D' of the secondary particle 110 increases, the delithiation voltage of the composite lithium supplement material 100 increases, and the charging capacity when the cut-off voltage is 4.1V and the charging capacity when the cut-off voltage is 4.3V decrease. This is because: as the particle size of the secondary particle 110 increases, during the charge and discharge process, the diffusion path of the lithium ions in the secondary particle 110 is The longer it is, the greater the resistance to the deintercalation of lithium ions from the secondary particles 110, which reduces the efficiency of the lithium ions of the secondary particles 110 being sequentially deintercalated from the secondary particles 110 and the modified layer 120 into the electrolyte and embedded into the negative electrode side, thereby reducing the lithium replenishment performance of the composite lithium replenishing material 100, thereby making the delithiation potential of the composite lithium replenishing material 100 of Example 10 higher, and the charging specific capacity when the cut-off voltage is 4.1V and the charging specific capacity when the cut-off voltage is 4.3V smaller.
[0220] Specifically, referring to Example 9 and Comparative Example 7, the composite lithium supplement material 100 of Example 9 includes an ion conductive layer 130, while the composite lithium supplement material 100 of Comparative Example 7 does not include the ion conductive layer 130, which makes the delithiation voltage of the composite lithium supplement material 100 of Example 9 lower than the delithiation voltage of the composite lithium supplement material 100 of Comparative Example 7, and the charging capacity of the secondary battery of Example 9 at a cut-off voltage of 4.1V is higher than the charging capacity of the secondary battery of Comparative Example 7 at a cut-off voltage of 4.1V, and the charging capacity of the secondary battery of Example 9 at a cut-off voltage of 4.3V is higher than the charging capacity of the secondary battery of Comparative Example 7 at a cut-off voltage of 4.3V. This is because: the ion conductive layer 130 is equivalent to providing another coating layer on the periphery of the modified layer 120 to prevent the modified layer 120 from rupturing and causing other substances in the electrolyte to directly contact the primary particles 112, so that the composite lithium supplement material 100 has higher stability. When the composite lithium supplement material 100 is applied to a secondary battery, it is beneficial to stabilize the interface structure between the positive electrode and the electrolyte, thereby reducing the side reaction between the electrolyte and the composite lithium supplement material 100 and improving the cycle stability of the secondary battery.
[0221] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, provided that there is no contradiction between them.
[0222] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.
Claims
1. A composite lithium supplement material, characterized in that: The composite lithium supplement material includes secondary particles, the secondary particles include multiple primary particles and functional additives, at least part of the functional additives are distributed between the multiple primary particles, the primary particles are lithium-rich particles, and the functional additives include one or more of a conductive agent, a dispersant and a catalyst.
2. The composite lithium supplement material according to claim 1, characterized in that: The functional additive is selected from a conductive agent, and the conductive agent includes cellulose nanocrystals. The cellulose nanocrystals shuttle between gaps between a plurality of primary particles and form a conductive network.
3. The composite lithium supplement material according to claim 2, characterized in that: The cellulose nanocrystal is a one-dimensional material, the diameter D of the one-dimensional material satisfies the range: 5nm≤D<200nm, and the length L of the one-dimensional material satisfies the range: 20nm≤L≤1000nm; and / or The particle size D' of the secondary particles satisfies the range of 0.3 μm ≤ D' ≤ 500 μm.
4. The composite lithium supplement material according to claim 1, characterized in that: The functional additive is selected from a catalyst, the catalyst includes a superlattice catalyst, the catalyst is in a particle form, and the catalyst is filled between the gaps of the plurality of primary particles.
5. The composite lithium supplement material according to claim 4, characterized in that: The superlattice catalyst is a stacked structure, comprising a plurality of metal compound layers and at least one intercalation layer, wherein both the metal compound layer and the intercalation layer extend along a first direction, and along a second direction, the intercalation layer is inserted between two adjacent metal compound layers, and the intercalation layer comprises a carbon layer, wherein the first direction and the second direction intersect.
6. The composite lithium supplement material according to claim 5, characterized in that: The superlattice catalyst further includes a carbon substrate, and the plurality of metal compound layers and at least one intercalation layer are disposed on the surface of the carbon substrate.
7. The composite lithium supplement material according to claim 1, characterized in that: The functional additive is selected from a dispersant, and the dispersant includes an anchoring group and a polymer segment, wherein the anchoring group is connected to the surface of the primary particle, one end of the polymer segment is connected to the anchoring group, and the other end of the polymer segment extends in a direction away from the primary particle.
8. The composite lithium supplement material according to any one of claims 1 to 7, characterized in that: The composite lithium supplement material further comprises a coating layer, which is coated on the outer surface of the secondary particles, and the coating layer comprises an acid-base complex containing lithium and / or an ion-conducting material.
9. A method for preparing a composite lithium supplement material, characterized in that: The preparation method comprises: Providing functional additives and primary particles, wherein the primary particles are lithium-rich particles, and the functional additives include one or more of a conductive agent, a dispersant, and a catalyst; The functional additive is mixed and dispersed with the primary particles so that at least part of the functional additive is distributed among a plurality of primary particles to obtain secondary particles.
10. A secondary battery, characterized in that: The invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the composite lithium supplement material according to any one of claims 1 to 8 and / or the composite lithium supplement material prepared by the preparation method of the composite lithium supplement material according to claim 9.
Citation Information
Cited By
Preparation method of composite coating modified Li5FeO4
CN121922594A